Solid forms of hemoglobin regulators

JP2024520897A5Pending Publication Date: 2025-05-01GLOBAL BLOOD THERAPEUTICS INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023569774
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-05-14
Filing Date
2022-05-13
Publication Date
2025-05-01

AI Technical Summary

Technical Problem

There is a need for highly pure solid forms of Compound I that are effective in treating diseases regulated by hemoglobin, such as sickle cell disease, which are not adequately addressed by existing formulations.

Method used

The development of various solid forms of Compound I, including crystalline and amorphous forms, as well as salts and solvates, which are characterized by specific X-ray diffraction patterns, thermal stability, and hygroscopicity, providing enhanced therapeutic efficacy.

Benefits of technology

These solid forms of Compound I exhibit improved stability and purity, enabling effective treatment of hemoglobin-mediated disorders by modulating hemoglobin function and reducing polymerization of sickle cells, thereby alleviating symptoms of sickle cell disease.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

Forms of (S)-2-hydroxy-6-((4-(2-(2-hydroxyethyl)nicotinoyl)morpholin-3-yl)methoxy)benzaldehyde (Compound I), or salts or solvates thereof, have been prepared and characterized in the solid state. Also provided are methods of making and using forms of Compound I. [Formula 1] TIFF2024520897000015.tif5441 [Figure 1] TIFF2024520897000016.tif81129
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit under 35 U.S.C. §119(e) of U.S. Provisional Application No. 63 / 188,833, filed May 14, 2021, which is incorporated by reference herein in its entirety.

[0002] FIELD OF THE DISCLOSURE This disclosure relates generally to solid forms of hemoglobin regulating compounds, pharmaceutical compositions thereof, therapeutic uses thereof, and methods of making the solid forms. [Background technology]

[0003] Sickle cell disease is a disorder of red blood cells, especially among people of African and Mediterranean descent. The basis of sickle cell disease is found in sickle cell hemoglobin (HbS), which contains a point mutation related to the common peptide sequence of hemoglobin A (HbA).

[0004] Hemoglobin (Hb) transports oxygen molecules from the lungs to various tissues and organs of the body. Hemoglobin binds and releases oxygen through conformational changes. Sickle cell hemoglobin (HbS) contains a point mutation in which glutamic acid is replaced by valine, which makes HbS prone to polymerization under hypoxic conditions and gives HbS-containing red blood cells their characteristic sickle shape. Sickle cells are also stiffer than normal red blood cells, and their lack of flexibility can cause blockage of blood vessels.

[0005] Compounds that regulate hemoglobin and are useful for treating disorders mediated by abnormal Hb (such as HbS), such as Compound I, are disclosed in U.S. Pat. No. 10,683,285, the disclosure of which is incorporated herein by reference in its entirety. Summary of the Invention [Problem to be solved by the invention]

[0006] There remains a need for highly pure solid forms of Compound I that are effective in treating diseases regulated by hemoglobin. [Means for solving the problem]

[0007] The present disclosure provides a solid form of Compound I of the formula:

[0008] [ka] and salts and solvates thereof. Also described herein are methods of making forms of Compound I, pharmaceutical compositions comprising solid forms of Compound I, and methods of using such forms and pharmaceutical compositions in the treatment of diseases regulated by hemoglobin. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 shows the X-ray powder diffraction (XRPD) of Form I of Compound I. [Figure 2A] FIG. 2 shows the differential scanning calorimetry (DSC) curve of Form I of Compound I. [Figure 2B] FIG. 2 shows another differential scanning calorimeter (DSC) curve of Form I of Compound I. [Diagram 3] FIG. 1 shows a thermogravimetric analysis (TGA) of Form I of Compound I. [Figure 4] FIG. 2 shows the dynamic vapor sorption (DVS plot) of Form I of Compound I. [Diagram 5] FIG. 2 shows the X-ray powder diffraction (XRPD) of material II of compound I. [Figure 6] FIG. 2 shows the differential scanning calorimeter (DSC) curve of material II of compound I. [Figure 7] FIG. 2 shows the thermogravimetric analysis (TGA) of material II of compound I. [Figure 8] FIG. 1 shows the dynamic vapor sorption (DVS) plot of material II of compound I. [Figure 9] FIG. 1 shows the X-ray powder diffraction (XRPD) of Compound I HCl Form A. [Figure 10] FIG. 2 shows the differential scanning calorimetry (DSC) curve of HCl Form A of Compound I. [Figure 11] FIG. 2 shows the thermogravimetric analysis (TGA) of Compound I HCl Form A. [Figure 12] FIG. 2 shows the dynamic vapor sorption (DVS plot) of HCl Form A of Compound I. [Figure 13] FIG. 2 shows the X-ray powder diffraction (XRPD) of amorphous Compound I. [Figure 14] FIG. 2 is a diagram showing a differential scanning calorimeter (DSC) curve of amorphous Compound I. [Figure 15] FIG. 2 shows the thermogravimetric analysis (TGA) of amorphous Compound I. [Figure 16] FIG. 2 shows the dynamic vapor sorption (DVS plot) of amorphous Compound I. [Figure 17] FIG. 2 shows the X-ray powder diffraction (XRPD) of besylate Form A of Compound I. [Figure 18] FIG. 2 shows a differential scanning calorimeter (DSC) curve of besylate salt Form A of Compound I. [Figure 19] FIG. 2 shows the thermogravimetric analysis (TGA) of besylate salt Form A of Compound I. [Figure 20] FIG. 2 shows the X-ray powder diffraction (XRPD) of edisylate salt Form A of Compound I. [Figure 21] FIG. 2 shows the differential scanning calorimeter (DSC) curve of edisylate salt Form A of Compound I. [Figure 22] FIG. 2 shows the thermogravimetric analysis (TGA) of edisylate salt Form A of Compound I. [Diagram 23] FIG. 2 shows the X-ray powder diffraction (XRPD) of Compound I edisylate material B. [Figure 24] FIG. 2 shows the differential scanning calorimeter (DSC) curve of compound I edisylate salt material B. [Diagram 25] FIG. 2 shows the thermogravimetric analysis (TGA) of Compound I edisylate material B. [Figure 26] FIG. 2 shows the X-ray powder diffraction (XRPD) of esylate salt Form A of Compound I. [Figure 27] FIG. 2 shows a differential scanning calorimeter (DSC) curve of esylate salt Form A of Compound I. [Figure 28] FIG. 2 shows the thermogravimetric analysis (TGA) of esylate salt Form A of Compound I. [Figure 29] FIG. 2 shows the X-ray powder diffraction (XRPD) of esylate salt Form B of Compound I. [Diagram 30] FIG. 2 shows the differential scanning calorimetry (DSC) curve of esylate salt Form B of Compound I. [Diagram 31] FIG. 2 shows the thermogravimetric analysis (TGA) of esylate salt Form B of Compound I. [Diagram 32] FIG. 1 shows the X-ray powder diffraction (XRPD) of napadilate salt Form A of Compound I. [Diagram 33] FIG. 2 shows the differential scanning calorimeter (DSC) curve of napadylate salt Form A of Compound I. [Diagram 34] FIG. 2 shows the thermogravimetric analysis (TGA) of napadylate salt Form A of Compound I. [Diagram 35] FIG. 2 shows the X-ray powder diffraction (XRPD) of napadylate salt material B of Compound I. [Diagram 36] FIG. 2 shows the differential scanning calorimeter (DSC) curve of napadylate salt material B of Compound I. [Figure 37] FIG. 2 shows the thermogravimetric analysis (TGA) of Compound I napadylate material B. [Figure 38] FIG. 2 shows the X-ray powder diffraction (XRPD) of napsylate salt Form A of Compound I. [Figure 39] FIG. 2 shows the X-ray powder diffraction (XRPD) of Compound I napsylate material B. [Diagram 40] FIG. 2 shows a differential scanning calorimeter (DSC) curve of Compound I napsylate salt material B. [Diagram 41] FIG. 2 shows the thermogravimetric analysis (TGA) of Compound I napsylate material B. [Diagram 42] FIG. 2 shows the X-ray powder diffraction (XRPD) of Compound I oxalate material A. [Diagram 43]FIG. 2 shows a differential scanning calorimeter (DSC) curve of Compound I oxalate material A. [Diagram 44] FIG. 2 shows the thermogravimetric analysis (TGA) of Compound I oxalate material A. [Diagram 45] FIG. 2 shows the X-ray powder diffraction (XRPD) of Compound I, oxalate Form B. [Diagram 46] FIG. 2 shows the differential scanning calorimetry (DSC) curve of Compound I oxalate Form B. [Figure 47] FIG. 2 shows the thermogravimetric analysis (TGA) of Compound I oxalate Form B. [Figure 48] FIG. 2 shows the X-ray powder diffraction (XRPD) of sulfate salt Form A of Compound I. [Figure 49] FIG. 2 shows a differential scanning calorimeter (DSC) curve of sulfate salt Form A of Compound I. [Figure 50] FIG. 2 shows a thermogravimetric analysis (TGA) of sulfate salt Form A of Compound I. [Figure 51] FIG. 2 shows the X-ray powder diffraction (XRPD) of Compound I tosylate Form A. [Figure 52] FIG. 2 shows a differential scanning calorimeter (DSC) curve of the tosylate salt Form A of Compound I. [Diagram 53] FIG. 2 shows the thermogravimetric analysis (TGA) of Compound I tosylate Form A. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The compound (S)-2-hydroxy-6-((4-(2-(2-hydroxyethyl)nicotinoyl)morpholin-3-yl)methoxy)benzaldehyde, referred to herein as Compound I, has the formula:

[0011] [ka]

[0012] Compound I is a modulator of hemoglobin. Its synthesis and methods of use are described in U.S. Patent No. 10,683,285, and U.S. Provisional Patent Application No. 63 / 188,735, filed May 14, 2021, entitled "Methods of Making a Modulator of Hemoglobin," and in a PCT application filed the same day herewith, entitled "Methods of Making a Modulator of Hemoglobin," all of which are incorporated herein by reference in their entirety.

[0013] The present disclosure relates to various solid forms of Compound I and methods of making such solid forms. For example, in some embodiments, the solid form of Compound I can include a salt or solvate of Compound I. In some embodiments, the solid form of Compound I can include an amorphous form, referred to herein as "amorphous Compound I."

[0014] The present disclosure relates to various crystalline forms of Compound I and methods of making the crystalline forms thereof. The crystalline forms of Compound I described herein include "Compound I Form I" and "Compound I Material II." In some embodiments, such forms of Compound I may be anhydrous.

[0015] Further described herein are additional crystalline forms of Compound I. In some embodiments, the crystalline form of Compound I can include a salt of Compound I. In some embodiments, the crystalline salt form of Compound I can be anhydrous or a solvate.

[0016] Some embodiments include Compound I:

[0017] [ka] wherein X is benzenesulfonic acid, 1,2-ethanedisulfonic acid, ethanesulfonic acid, naphthalene-1,5-disulfonic acid, naphthalene-2-sulfonic acid, oxalic acid, sulfuric acid, or p-toluenesulfonic acid, and the ratio of compound I to X is 1:1 or 2:1, or a solvate thereof.

[0018] In some embodiments, X can be hydrochloric acid, benzenesulfonic acid, 1,2-ethanedisulfonic acid, ethanesulfonic acid, naphthalene-1,5-disulfonic acid, naphthalene-2-sulfonic acid, oxalic acid, sulfuric acid, or p-toluenesulfonic acid. Further described herein are the following exemplary forms: "HCl Form A of Compound I", "Besylate Form A of Compound I", "Edisylate Form A of Compound I", "Edisylate Material B of Compound I", "Esylate Form A of Compound I", "Esylate Form B of Compound I", "Napadilate Form A of Compound I", "Napadilate Material B of Compound I", "Napsylate Form A of Compound I", "Napsylate Material B of Compound I", "Oxalate Material A of Compound I", "Oxalate Form B of Compound I", "Sulfate Form A of Compound I", and "Tosylate Form A of Compound I".

[0019] In some embodiments, the crystalline salt form or solvate thereof is selected from the group consisting of besylate Form A of Compound I, edisylate Form A of Compound I, edisylate material B of Compound I, esylate Form A of Compound I, esylate Form B of Compound I, napadilate Form A of Compound I, napadilate material B of Compound I, napsylate Form A of Compound I, napsylate material B of Compound I, oxalate material A of Compound I, oxalate Form B of Compound I, sulfate Form A of Compound I, and tosylate Form A of Compound I.

[0020] In some embodiments, HCl Form A of Compound I, oxalate Form B of Compound I, or sulfate Form A of Compound I is provided.

[0021] 1.Definition As used herein, the following words and phrases are generally intended to have the meanings set forth below, unless the context in which they are used indicates otherwise.

[0022] The term "comprise" and variations thereof, such as "comprises" and "comprising," should be interpreted in an open and inclusive sense, i.e., "including, but not limited to." Furthermore, the singular forms "a," "an," and "the" include plural references unless the context clearly dictates otherwise. Thus, reference to a "compound" includes a plurality of such compounds, and reference to an "assay" includes reference to one or more assays and equivalents thereof known to those of skill in the art.

[0023] Reference herein to "about" a value or parameter includes (and describes) embodiments directed to the value or parameter itself. In certain embodiments, the term "about" includes ±10% of the indicated amount. In other embodiments, the term "about" includes ±5% of the indicated amount. In certain other embodiments, the term "about" includes ±2.5% of the indicated amount. In certain other embodiments, the term "about" includes ±1% of the indicated amount. Also, the term "about X" includes the description of "X".

[0024] Recitations of numerical ranges of values ​​throughout this disclosure are intended to serve as a shorthand notation for referring individually to each separate value falling within the range, inclusive of the values ​​defining the range, and each separate value is incorporated herein as if it were individually referenced herein.

[0025] Forms of Compound I or salts or solvates thereof are provided herein. In some embodiments, reference to a form of Compound I or a salt or solvate thereof means that at least 50%-99% (e.g., at least 50%, at least 55%, at least 60%, at least 65%, at least 70%, at least 75%, at least 80%, at least 85%, at least 90%, at least 95%, or at least 99%) of Compound I or its salt or solvate present in the composition is in the specified form. For example, in some embodiments, reference to Form I of Compound I means that at least 50%, at least 55%, at least 60%, at least 65%, at least 70%, at least 75%, at least 80%, at least 85%, at least 90%, at least 95%, or at least 99% of Compound I present in the composition is in Form I.

[0026] The term "solid form" refers to a type of solid state material, including amorphous and crystalline forms. The term "crystalline form" refers to polymorphs, solvates, and the like. The term "polymorph" refers to a particular crystal structure that has particular physical properties, such as X-ray diffraction and melting point.

[0027] The term "solvate" refers to a complex formed by the combination of solvent molecules with molecules or ions of the solute. The solvent may be an organic compound, an inorganic compound, or a mixture of both. Some examples of solvents include, but are not limited to, methanol, N,N-dimethylformamide, tetrahydrofuran, dimethylsulfoxide, and water. In general, the solvated forms are equivalent to the unsolvated forms and are included within the scope of the present disclosure.

[0028] The term "desolvated" refers to a form of Compound I, a solvate as described herein, from which the solvent molecules have been partially or completely removed. Desolvation techniques for producing desolvated forms include, but are not limited to, exposing a form (solvate) of Compound I to a vacuum, exposing the solvate to high temperature, exposing the solvate to a stream of gas such as air or nitrogen, or any combination thereof. Thus, a desolvated form of Compound I can be anhydrous, i.e., completely free of solvent molecules, or a partial solvate in which the solvent molecules are present in stoichiometric or non-stoichiometric amounts.

[0029] The term "amorphous" refers to a state in which a material lacks long-range order at the molecular level and may exhibit the physical properties of a solid or liquid, depending on temperature. Typically, such materials do not exhibit distinctive X-ray diffraction patterns and exhibit the properties of a solid, but are more formally described as a liquid. Upon heating, a change in properties from solid to liquid occurs that is characterized by a change of state, usually second order (glass transition).

[0030] Any formula or structure shown herein, including compound I, is also intended to represent unlabeled forms of the compound as well as isotopically labeled forms.It is understood that for any given atom, isotopes may be present essentially in proportions according to their natural abundance, or one or more specific atoms may be enriched with one or more isotopes using synthetic methods known to those skilled in the art.Thus, hydrogen may be, for example, 1 H, 2 H, 3 H, and carbon is, for example, 11 C. 12 C. 13 C. 14 C, and oxygen is, for example, 16 O. 17 O. 18 O, and nitrogen is, for example, 13 N, 14 N, 15 N, and sulfur, for example, 32 S, 33 S, 34 S, 35S, 36 S, 37 S, 38 S, fluoro is, for example, 17 F, 18 F, 19 F, and chloro, for example: 35 Cl, 36 Cl, 37 Cl, 38 Cl, 39 Contains Cl and other similar species.

[0031] "Pharmaceutically acceptable" or "physiologically acceptable" refers to forms, compositions, dosage forms, and other materials described herein that are useful in the preparation of pharmaceutical compositions suitable for veterinary or human pharmaceutical use.

[0032] The term "pharmaceutically acceptable salt" of a given compound refers to a salt that retains the biological effectiveness and properties of the given compound and is not biologically or otherwise undesirable. "Pharmaceutically acceptable salt" or "physiologically acceptable salt" includes, for example, salts with inorganic acids and salts with organic acids. Furthermore, when the forms described herein are obtained as acid addition salts, the free base can be obtained by basifying a solution of the acid salt. In contrast, when the product is a free base, an addition salt, particularly a pharmaceutically acceptable addition salt, can be produced by dissolving the free base in a suitable organic solvent and treating the solution with an acid according to conventional procedures for preparing acid addition salts from basic compounds. Those skilled in the art will recognize various synthetic methods that can be used to prepare non-toxic pharmaceutically acceptable addition salts. Pharmaceutically acceptable acid addition salts can be prepared from inorganic and organic acids. Salts derived from inorganic acids include, for example, hydrochloric acid, hydrobromic acid, sulfuric acid, nitric acid, phosphoric acid, and the like. Salts derived from organic acids include, for example, acetic acid, propionic acid, gluconic acid, glycolic acid, pyruvic acid, oxalic acid, malic acid, malonic acid, succinic acid, maleic acid, fumaric acid, tartaric acid, citric acid, benzoic acid, cinnamic acid, mandelic acid, methanesulfonic acid, ethanesulfonic acid, p-toluenesulfonic acid, salicylic acid, etc. Similarly, pharmaceutically acceptable base addition salts can be prepared from inorganic and organic bases. Salts derived from inorganic bases include, by way of example only, sodium, potassium, lithium, aluminum, ammonium, calcium, and magnesium salts. Salts derived from organic bases include, but are not limited to, salts of primary, secondary, and tertiary amines. Specific examples of suitable amines include, by way of example only, isopropylamine, trimethylamine, diethylamine, tri(iso-propyl)amine, tri(n-propyl)amine, ethanolamine, 2-dimethylaminoethanol, piperazine, piperidine, morpholine, N-ethylpiperidine, etc. In some embodiments, pharma- ceutically acceptable salts do not include salts of primary amines.

[0033] In some embodiments, the phrases "substantially shown in FIG." or "substantially shown in Figure" when applied to X-ray powder diffractograms means including a variation of ±0.2°2θ or ±0.1°2θ, when applied to DSC thermograms means including a variation of ±3° C., and when applied to thermogravimetric analysis (TGA) means including a variation of ±2% in weight loss.

[0034] 2. Form of Compound I As generally described above, the present disclosure provides crystalline forms, and salts or solvates thereof, of Compound I. Additional forms, including amorphous forms, are further described herein.

[0035] It should be noted that crystalline forms of Compound I, and salts or solvates thereof, as well as other forms of Compound I (e.g., amorphous forms), and salts or solvates thereof, are collectively referred to herein as "forms of Compound I."

[0036] In some embodiments, compound I is a salt. In some embodiments, compound I is a pharma- ceutically acceptable salt. In some embodiments, compound I is a solvate. In some embodiments, compound I is a salt or a solvate salt.

[0037] In some embodiments, Compound I is in an amorphous form.

[0038] Form I of Compound I Form I of Compound I is contemplated to be, monotropically, thermodynamically more stable as compared to Form II of Compound I.

[0039] The present disclosure provides, in some embodiments, a crystalline form of Compound I characterized by an X-ray powder diffractogram containing the following peaks as determined with a diffractometer using Cu-Kα radiation: 18.3, 23.4, and 26.1 °2θ±0.2 °2θ (Form I of Compound I).

[0040] In some embodiments, the diffractogram of Form I of Compound I further comprises one or more peaks at 10.8 or 17.3 °2θ±0.2 °2θ.

[0041] In some embodiments, the crystalline form of Compound I is characterized by an X-ray powder diffractogram containing the following peaks as determined by a diffractometer using Cu-Kα radiation: 10.8 and 23.4 °2θ±0.2 °2θ (Form I of Compound I). In some embodiments, the crystalline form of Compound I is characterized by an X-ray powder diffractogram containing the following peaks as determined by a diffractometer using Cu-Kα radiation: 10.8, 23.4, and 26.1 °2θ±0.2 °2θ (Form I of Compound I). In some embodiments, the diffractogram of Form I of Compound I further contains one or more peaks at 17.3, 17.5, or 23.7 °2θ±0.2 °2θ.

[0042] In some embodiments, Form I of Compound I is characterized by an X-ray powder diffractogram substantially as shown in FIG.

[0043] In some embodiments, Form I of Compound I is characterized by a differential scanning calorimetry (DSC) curve that includes an endotherm at about 111° C. (onset temperature). In some embodiments, Form I of Compound I is characterized by a DSC curve substantially as shown in FIG. 2A.

[0044] In some embodiments, Form I of Compound I is characterized by a thermogravimetric analysis (TGA) thermogram that exhibits negligible weight loss upon heating to 192° C. In some embodiments, Form I of Compound I is characterized by a thermogram substantially as shown in FIG.

[0045] Some embodiments provide Form I of Compound I, having unit cell parameters: a=5.50599(10) Å, b=16.4086(2) Å, c=20.4992(4) Å, α=90°, β=90°, and γ=90°.

[0046] In some embodiments, Form I of Compound I has unit cell parameters: a=5.50599(10) Å, b=16.4086(2) Å, c=20.4992(4) Å, α=90°, β=90°, and γ=90°, and volume=1852.02(5) Å 3 In some embodiments, Form I of Compound I is characterized by one or more of the crystal structure parameters in Table 1.

[0047] In some embodiments, a method of making Form I of Compound I is provided. In some embodiments, the method of making Form I of Compound I includes: combining Compound I and a solvent to form a mixture; heating the mixture; cooling the mixture to form a slurry; filtering the slurry to obtain a solid; drying the solid to obtain Form I of Compound I; Includes.

[0048] In some embodiments, the solvent is an organic solvent. In some embodiments, the organic solvent is ethyl acetate. In some embodiments, the organic solvent is acetonitrile. In some embodiments, the organic solvent is acetone. In some embodiments, the organic solvent is a mixture of acetone and methyl tert-butyl ether (MTBE).

[0049] In some embodiments, heating the mixture includes heating the mixture until Compound I dissolves in the mixture such that the mixture is a clear solution. In some embodiments, heating the mixture further includes adding (while heating) a second solvent. In some embodiments, the second solvent is MTBE. In some embodiments, cooling the mixture to form a slurry includes cooling the mixture to ambient temperature. In some embodiments, cooling the mixture to form a slurry includes cooling the mixture to ambient temperature and stirring for about 18 to 24 hours. In some embodiments, cooling the mixture includes adding a third solvent. In some embodiments, the third solvent is MTBE. In some embodiments, drying the solid includes drying under vacuum at about 45° C. to about 55° C.

[0050] Material II of Compound I (also referred to as Form II of Compound I) The present disclosure provides, in some embodiments, a crystalline form of Compound I characterized by an X-ray powder diffractogram containing the following peaks: 14.9, 16.7, and 22.9°2θ±0.2°2θ (Material II of Compound I) as determined with a diffractometer using Cu-Kα radiation.

[0051] In some embodiments, the diffractogram of material II of compound I further comprises one or more peaks at 18.4 or 19.2 degrees 2θ±0.2 degrees 2θ.

[0052] In some embodiments, the crystalline form of Compound I is characterized by an X-ray powder diffractogram containing the following peaks: 14.9, 22.6, and 25.8 °2θ±0.2 °2θ (Material II of Compound I) as determined with a diffractometer using Cu-Kα radiation. In some embodiments, the diffractogram of Material II of Compound I further contains one or more peaks at 18.6, 19.6, or 20.2 °2θ±0.2 °2θ.

[0053] In some embodiments, material II of compound I is characterized by an X-ray powder diffractogram substantially as shown in FIG.

[0054] In some embodiments, material II of compound I is characterized by a differential scanning calorimetry (DSC) curve that includes an endotherm at about 102° C. (onset temperature). In some embodiments, material II of compound I is characterized by a DSC curve substantially as shown in FIG.

[0055] In some embodiments, material II of Compound I is characterized by a thermogravimetric analysis (TGA) thermogram that exhibits negligible weight loss upon heating to 195° C. In some embodiments, material II of Compound I is characterized by a thermogram substantially as shown in FIG.

[0056] Compound I HCl Form A The present disclosure provides, in some embodiments, a compound of the formula:

[0057] [ka] and an X-ray powder diffractogram containing the following peaks, as determined with a diffractometer using Cu-Kα radiation: 12.7, 16.4, and 23.5°2θ±0.2°2θ (HCl Form A of Compound I).

[0058] In some embodiments, the diffractogram of HCl Form A of compound I further comprises one or more peaks at 16.7 or 18.5 °2θ±0.2 °2θ. In some embodiments, HCl Form A of compound I is characterized by an X-ray powder diffractogram substantially as shown in FIG.

[0059] In some embodiments, HCl Form A of Compound I is characterized by a differential scanning calorimetry (DSC) curve that includes an endotherm at about 193° C. (onset temperature). In some embodiments, HCl Form A of Compound I is characterized by a DSC curve substantially as shown in FIG.

[0060] In some embodiments, HCl Form A of Compound I is characterized by a thermogravimetric analysis (TGA) thermogram exhibiting a weight loss of 0.6% upon heating to 188° C. In some embodiments, HCl Form A of Compound I is characterized by a thermogram substantially as shown in FIG.

[0061] Some embodiments provide HCl Form A of Compound I, having unit cell parameters: a=7.72088(10) Å, b=7.57161(10) Å, c=17.6273(2) Å, α=90°, β=98.0066(12)°, and γ=90°.

[0062] In some embodiments, HCl Form A of Compound I has unit cell parameters: a=7.72088(10) Å, b=7.57161(10) Å, c=17.6273(2) Å, α=90°, β=98.0066(12)°, and γ=90°, and volume=1022.44(2) Å 3 has.

[0063] In some embodiments, HCl Form A of Compound I is characterized by one or more of the crystal structure parameters in Table 3.

[0064] Besylate Form A of Compound I The disclosure provides, in some embodiments, a crystalline form of (S)-2-hydroxy-6-((4-(2-(2-hydroxyethyl)nicotinoyl)morpholin-3-yl)methoxy)benzaldehyde besylate ("besylate Form A of Compound I" or "besylate Form A") characterized by an X-ray powder diffractogram comprising the following peaks as determined with a diffractometer using Cu-Kα radiation: 4.93, 17.0, 18.5, and 19.2 °2θ ± 0.2 °2θ. In some embodiments, the diffractogram of besylate Form A of Compound I further comprises one or more peaks at 15.7 and 22.4 °2θ ± 0.2 °2θ. In some embodiments, besylate Form A of Compound I is characterized by an X-ray powder diffractogram substantially as shown in FIG. 17.

[0065] In some embodiments, the besylate salt Form A of Compound I is characterized by a differential scanning calorimetry (DSC) curve that includes an endotherm at about 114° C. (peak temperature). In some embodiments, the besylate salt Form A of Compound I is characterized by a differential scanning calorimetry (DSC) curve that includes an endotherm at about 130° C. (peak temperature). In some embodiments, the besylate salt Form A of Compound I is characterized by a DSC curve substantially as shown in FIG.

[0066] In some embodiments, the besylate salt Form A of Compound I is characterized by a thermogravimetric analysis (TGA) thermogram exhibiting a weight loss of about 3.9% up to 145° C. In some embodiments, the besylate salt Form A of Compound I is characterized by a thermogravimetric analysis (TGA) thermogram exhibiting a weight loss of about 6.6% from 145° C. to 211° C. In some embodiments, the besylate salt Form A of Compound I is characterized by a thermogram substantially as depicted in FIG.

[0067] Edisilate Form A of Compound I The disclosure provides, in some embodiments, a crystalline form of (S)-2-hydroxy-6-((4-(2-(2-hydroxyethyl)nicotinoyl)morpholin-3-yl)methoxy)benzaldehyde edisylate ("edisylate Form A of Compound I" or "edisylate Form A") characterized by an X-ray powder diffractogram containing the following peaks: 11.5, 18.6, and 23.9 °2θ±0.2 °2θ as determined with a diffractometer using Cu-Kα radiation. In some embodiments, the diffractogram of edisylate Form A of Compound I further contains one or more peaks at 4.99 and 21.1 °2θ±0.2 °2θ. In some embodiments, edisylate Form A of Compound I is characterized by an X-ray powder diffractogram substantially as shown in FIG. 20.

[0068] In some embodiments, the edisylate salt Form A of Compound I is characterized by a differential scanning calorimetry (DSC) curve comprising an endotherm at about 91.4° C. (peak temperature). In some embodiments, the edisylate salt Form A of Compound I is characterized by a DSC curve substantially as shown in FIG.

[0069] In some embodiments, the edisylate salt Form A of Compound I is characterized by a thermogravimetric analysis (TGA) thermogram exhibiting a weight loss of about 0.8% up to 91° C. In some embodiments, the edisylate salt Form A of Compound I is characterized by a thermogram substantially as shown in FIG.

[0070] Compound I edisylate material B The present disclosure provides, in some embodiments, a crystalline form of (S)-2-hydroxy-6-((4-(2-(2-hydroxyethyl)nicotinoyl)morpholin-3-yl)methoxy)benzaldehyde edisylate ("edisylate material B of Compound I" or "edisylate material B") characterized by an X-ray powder diffractogram comprising the following peaks as determined with a diffractometer using Cu-Kα radiation: 14.6, 22.6, and 23.9 °2θ±0.2 °2θ. In some embodiments, the diffractogram of edisylate material B of Compound I further comprises one or more peaks at 19.0 and 26.7 °2θ±0.2 °2θ. In some embodiments, edisylate material B of Compound I is characterized by an X-ray powder diffractogram substantially as shown in FIG. 23.

[0071] In some embodiments, the edisylate salt material B of Compound I is characterized by a differential scanning calorimetry (DSC) curve that includes an endotherm at about 118° C. (peak temperature). In some embodiments, the edisylate salt material B of Compound I is characterized by a differential scanning calorimetry (DSC) curve that includes an endotherm at about 187° C. (peak temperature). In some embodiments, the edisylate salt material B of Compound I is characterized by a differential scanning calorimetry (DSC) curve that includes an endotherm at about 208° C. (peak temperature). In some embodiments, the edisylate salt material B of Compound I is characterized by a DSC curve substantially as shown in FIG.

[0072] In some embodiments, Compound I edisylate material B is characterized by a thermogravimetric analysis (TGA) thermogram exhibiting a weight loss of about 1.1% up to 204° C. In some embodiments, Compound I edisylate material B is characterized by a thermogram substantially as shown in FIG.

[0073] Essylate Form A of Compound I The disclosure provides, in some embodiments, a crystalline form of (S)-2-hydroxy-6-((4-(2-(2-hydroxyethyl)nicotinoyl)morpholin-3-yl)methoxy)benzaldehyde esylate ("esylate Form A of Compound I" or "esylate Form A") characterized by an X-ray powder diffractogram containing the following peaks: 18.5, 19.2, and 22.5 °2θ±0.2 °2θ as determined with a diffractometer using Cu-Kα radiation. In some embodiments, the diffractogram of esylate Form A of Compound I further contains one or more peaks at 11.2 and 21.4 °2θ±0.2 °2θ. In some embodiments, esylate Form A of Compound I is characterized by an X-ray powder diffractogram substantially as shown in FIG. 26.

[0074] In some embodiments, the esylate salt Form A of Compound I is characterized by a differential scanning calorimetry (DSC) curve comprising an endotherm at about 49.6° C. (peak temperature). In some embodiments, the esylate salt Form A of Compound I is characterized by a differential scanning calorimetry (DSC) curve comprising an endotherm at about 100° C. (peak temperature). In some embodiments, the esylate salt Form A of Compound I is characterized by a differential scanning calorimetry (DSC) curve comprising an endotherm at about 172° C. (peak temperature). In some embodiments, the esylate salt Form A of Compound I is characterized by a DSC curve substantially as depicted in FIG.

[0075] In some embodiments, the esylate salt Form A of Compound I is characterized by a thermogravimetric analysis (TGA) thermogram exhibiting a weight loss of about 3.8% up to 91° C. In some embodiments, the esylate salt Form A of Compound I is characterized by a thermogravimetric analysis (TGA) thermogram exhibiting a weight loss of about 17.6% from 93° C. to 170° C. In some embodiments, the esylate salt Form A of Compound I is characterized by a thermogram substantially as depicted in FIG.

[0076] Essylate Form B of Compound I The disclosure provides, in some embodiments, a crystalline form of (S)-2-hydroxy-6-((4-(2-(2-hydroxyethyl)nicotinoyl)morpholin-3-yl)methoxy)benzaldehyde esylate ("esylate Form B of Compound I" or "esylate Form B") characterized by an X-ray powder diffractogram comprising the following peaks: 5.52, 19.8, and 22.7 °2θ±0.2 °2θ as determined with a diffractometer using Cu-Kα radiation. In some embodiments, the diffractogram of esylate Form B of Compound I further comprises one or more peaks at 10.8 and 16.8 °2θ±0.2 °2θ. In some embodiments, esylate Form B of Compound I is characterized by an X-ray powder diffractogram substantially as shown in FIG. 29.

[0077] In some embodiments, the esylate salt Form B of Compound I is characterized by a differential scanning calorimetry (DSC) curve comprising an endotherm at about 97.0° C. (onset temperature). In some embodiments, the esylate salt Form B of Compound I is characterized by a DSC curve substantially as shown in FIG.

[0078] In some embodiments, the esylate salt Form B of Compound I is characterized by a thermogravimetric analysis (TGA) thermogram exhibiting a weight loss of about 2.6% up to 117° C. In some embodiments, the esylate salt Form B of Compound I is characterized by a thermogram substantially as shown in FIG.

[0079] Napadylate Form A of Compound I The disclosure provides, in some embodiments, a crystalline form of (S)-2-hydroxy-6-((4-(2-(2-hydroxyethyl)nicotinoyl)morpholin-3-yl)methoxy)benzaldehyde napadilate ("napadilate Form A of Compound I" or "napadilate Form A") characterized by an X-ray powder diffractogram containing the following peaks as determined with a diffractometer using Cu-Kα radiation: 5.26, 10.6, 12.1, and 17.8 °2θ±0.2 °2θ. In some embodiments, the diffractogram of napadilate Form A of Compound I further contains one or more peaks at 19.5 and 20.7 °2θ±0.2 °2θ. In some embodiments, napadilate Form A of Compound I is characterized by an X-ray powder diffractogram substantially as shown in FIG. 32.

[0080] In some embodiments, napadilate Form A of Compound I is characterized by a differential scanning calorimetry (DSC) curve that includes an endotherm at about 69.8° C. (peak temperature). In some embodiments, napadilate Form A of Compound I is characterized by a differential scanning calorimetry (DSC) curve that includes an endotherm at about 151° C. (peak temperature). In some embodiments, napadilate Form A of Compound I is characterized by a differential scanning calorimetry (DSC) curve that includes an endotherm at about 198° C. (peak temperature). In some embodiments, napadilate Form A of Compound I is characterized by a DSC curve substantially as shown in FIG.

[0081] In some embodiments, napadilate Form A of Compound I is characterized by a thermogravimetric analysis (TGA) thermogram exhibiting a weight loss of about 16.9% up to 117° C. In some embodiments, napadilate Form A of Compound I is characterized by a thermogravimetric analysis (TGA) thermogram exhibiting a weight loss of about 5.9% from 117° C. to 162° C. In some embodiments, napadilate Form A of Compound I is characterized by a thermogravimetric analysis (TGA) thermogram exhibiting a weight loss of about 3.7% from 163° C. to 225° C. In some embodiments, napadilate Form A of Compound I is characterized by a thermogram substantially as depicted in FIG.

[0082] Napadylate of Compound I Material B The present disclosure provides, in some embodiments, a crystalline form of (S)-2-hydroxy-6-((4-(2-(2-hydroxyethyl)nicotinoyl)morpholin-3-yl)methoxy)benzaldehyde napadilate ("Napadilate Material B of Compound I" or "Napadilate Material B") characterized by an X-ray powder diffractogram comprising the following peaks as determined with a diffractometer using Cu-Kα radiation: 5.02, 10.4, 18.1 °2θ±0.2 °2θ. In some embodiments, the diffractogram of Napadilate Material B of Compound I further comprises one or more peaks at 20.2 and 20.9 °2θ±0.2 °2θ. In some embodiments, Napadilate Material B of Compound I is characterized by an X-ray powder diffractogram substantially as shown in FIG. 35.

[0083] In some embodiments, the napadilate material B of Compound I is characterized by a differential scanning calorimetry (DSC) curve that includes an endotherm at about 77.1° C. (peak temperature). In some embodiments, the napadilate material B of Compound I is characterized by a differential scanning calorimetry (DSC) curve that includes an endotherm at about 158° C. (peak temperature). In some embodiments, the napadilate material B of Compound I is characterized by a DSC curve substantially as shown in FIG.

[0084] In some embodiments, the napadilate material B of Compound I is characterized by a thermogravimetric analysis (TGA) thermogram exhibiting a weight loss of about 5.5% up to 162° C. In some embodiments, the napadilate material B of Compound I is characterized by a thermogram substantially as shown in FIG.

[0085] Napsylate Form A of Compound I The disclosure provides, in some embodiments, a crystalline form of (S)-2-hydroxy-6-((4-(2-(2-hydroxyethyl)nicotinoyl)morpholin-3-yl)methoxy)benzaldehyde napsylate ("napsylate Form A of Compound I" or "napsylate Form A") characterized by an X-ray powder diffractogram comprising the following peaks: 15.0, 20.0, and 24.0 °2θ±0.2 °2θ as determined with a diffractometer using Cu-Kα radiation. In some embodiments, the diffractogram of napsylate Form A of Compound I further comprises one or more peaks at 15.1 and 17.4 °2θ±0.2 °2θ. In some embodiments, napsylate Form A of Compound I is characterized by an X-ray powder diffractogram substantially as shown in FIG. 38.

[0086] Napsyl salt of compound I Material B The disclosure provides, in some embodiments, a crystalline form of (S)-2-hydroxy-6-((4-(2-(2-hydroxyethyl)nicotinoyl)morpholin-3-yl)methoxy)benzaldehyde napsylate ("napsylate material B of Compound I" or "napsylate material B") characterized by an X-ray powder diffractogram comprising the following peaks as determined with a diffractometer using Cu-Kα radiation: 4.30, 18.5, and 19.0 °2θ±0.2 °2θ. In some embodiments, the diffractogram of napsylate material B of Compound I further comprises one or more peaks at 10.7 and 21.5 °2θ±0.2 °2θ. In some embodiments, napsylate material B of Compound I is characterized by an X-ray powder diffractogram substantially as shown in FIG. 39.

[0087] In some embodiments, the napsylate salt material B of Compound I is characterized by a differential scanning calorimetry (DSC) curve that includes an endotherm at about 52.0° C. (peak temperature). In some embodiments, the napsylate salt material B of Compound I is characterized by a differential scanning calorimetry (DSC) curve that includes an endotherm at about 111° C. (peak temperature). In some embodiments, the napsylate salt material B of Compound I is characterized by a differential scanning calorimetry (DSC) curve that includes an endotherm at about 177° C. (peak temperature). In some embodiments, the napsylate salt material B of Compound I is characterized by a DSC curve substantially as shown in FIG.

[0088] In some embodiments, Compound I napsylate material B is characterized by a thermogravimetric analysis (TGA) thermogram exhibiting a weight loss of about 3.0% up to 117° C. In some embodiments, Compound I napsylate material B is characterized by a thermogram substantially as shown in FIG.

[0089] Compound I Oxalate Material A The present disclosure provides, in some embodiments, a crystalline form of (S)-2-hydroxy-6-((4-(2-(2-hydroxyethyl)nicotinoyl)morpholin-3-yl)methoxy)benzaldehyde oxalate ("Compound I oxalate Material A" or "oxalate material A") characterized by an X-ray powder diffractogram comprising the following peaks as determined with a diffractometer using Cu-Kα radiation: 10.7, 11.6, and 16.9 °2θ±0.2 °2θ. In some embodiments, the diffractogram of Compound I oxalate Material A further comprises one or more peaks at 10.9 and 21.6 °2θ±0.2 °2θ. In some embodiments, Compound I oxalate Material A is characterized by an X-ray powder diffractogram substantially as shown in FIG. 42.

[0090] In some embodiments, Compound I oxalate material A is characterized by a differential scanning calorimetry (DSC) curve that includes an endotherm at about 67.6° C. (peak temperature). In some embodiments, Compound I oxalate material A is characterized by a differential scanning calorimetry (DSC) curve that includes an endotherm at about 111° C. (onset temperature). In some embodiments, Compound I oxalate material A is characterized by a DSC curve substantially as shown in FIG.

[0091] In some embodiments, Compound I oxalate material A is characterized by a thermogravimetric analysis (TGA) thermogram exhibiting a weight loss of about 1.3% up to 122° C. In some embodiments, Compound I oxalate material A is characterized by a thermogram substantially as shown in FIG.

[0092] Oxalate Form B of Compound I The disclosure provides, in some embodiments, a crystalline form of (S)-2-hydroxy-6-((4-(2-(2-hydroxyethyl)nicotinoyl)morpholin-3-yl)methoxy)benzaldehyde oxalate ("oxalate Form B of Compound I" or "oxalate Form B") characterized by an X-ray powder diffractogram containing the following peaks: 11.9, 16.6, and 20.2 °2θ ± 0.2 °2θ as determined with a diffractometer using Cu-Kα radiation. In some embodiments, the diffractogram of oxalate Form B of Compound I further contains one or more peaks at 18.1 and 23.3 °2θ ± 0.2 °2θ. In some embodiments, oxalate Form B of Compound I is characterized by an X-ray powder diffractogram substantially as shown in FIG. 45.

[0093] In some embodiments, the oxalate salt Form B of Compound I is characterized by a differential scanning calorimetry (DSC) curve comprising an endotherm at about 118° C. (onset temperature). In some embodiments, the oxalate salt Form B of Compound I is characterized by a DSC curve substantially as shown in FIG.

[0094] In some embodiments, the oxalate salt Form B of Compound I is characterized by a thermogravimetric analysis (TGA) thermogram exhibiting a weight loss of about 0.2% up to 128° C. In some embodiments, the oxalate salt Form B of Compound I is characterized by a thermogram substantially as shown in FIG.

[0095] Sulfate Form A of Compound I The disclosure provides, in some embodiments, a crystalline form of (S)-2-hydroxy-6-((4-(2-(2-hydroxyethyl)nicotinoyl)morpholin-3-yl)methoxy)benzaldehyde sulfate ("sulfate Form A of Compound I" or "sulfate Form A") characterized by an X-ray powder diffractogram comprising the following peaks: 10.7, 18.2, and 23.5 °2θ±0.2 °2θ as determined with a diffractometer using Cu-Kα radiation. In some embodiments, the diffractogram of sulfate Form A of Compound I further comprises one or more peaks at 11.6, 19.3, and 20.8 °2θ±0.2 °2θ. In some embodiments, sulfate Form A of Compound I is characterized by an X-ray powder diffractogram substantially as shown in FIG. 48.

[0096] In some embodiments, sulfate salt Form A of Compound I is characterized by a differential scanning calorimetry (DSC) curve that includes an endotherm at about 146° C. (onset temperature). In some embodiments, sulfate salt Form A of Compound I is characterized by a DSC curve substantially as shown in FIG.

[0097] In some embodiments, sulfate salt Form A of Compound I is characterized by a thermogravimetric analysis (TGA) thermogram exhibiting a weight loss of about 1.4% up to 161° C. In some embodiments, sulfate salt Form A of Compound I is characterized by a thermogram substantially as shown in FIG.

[0098] Tosylate Form A of Compound I The disclosure provides, in some embodiments, a crystalline form of (S)-2-hydroxy-6-((4-(2-(2-hydroxyethyl)nicotinoyl)morpholin-3-yl)methoxy)benzaldehyde tosylate ("tosylate Form A of Compound I" or "tosylate Form A") characterized by an X-ray powder diffractogram comprising the following peaks: 4.68, 17.7, and 23.4 °2θ ± 0.2 °2θ as determined with a diffractometer using Cu-Kα radiation. In some embodiments, the diffractogram of tosylate Form A of Compound I further comprises one or more peaks at 18.6 and 19.1 °2θ ± 0.2 °2θ. In some embodiments, tosylate Form A of Compound I is characterized by an X-ray powder diffractogram substantially as shown in FIG. 51.

[0099] In some embodiments, the tosylate salt Form A of Compound I is characterized by a differential scanning calorimetry (DSC) curve comprising an endotherm at about 115° C. (peak temperature). In some embodiments, the tosylate salt Form A of Compound I is characterized by a DSC curve substantially as shown in FIG.

[0100] In some embodiments, the tosylate salt Form A of Compound I is characterized by a thermogravimetric analysis (TGA) thermogram exhibiting a weight loss of about 3.3% up to 137° C. In some embodiments, the tosylate salt Form A of Compound I is characterized by a thermogram substantially as shown in FIG.

[0101] 3. Pharmaceutical Compositions and Methods of Administration The forms of Compound I described herein can be administered in pharmaceutical compositions.Therefore, the present invention provides pharmaceutical compositions that include one or more of the forms of Compound I described herein, or salts or solvates thereof, and one or more pharma- ceutically acceptable vehicles, such as carriers, adjuvants, and excipients.Suitable pharma-ceutically acceptable vehicles include, for example, inert solid diluents and fillers, diluents including sterile aqueous solutions and various organic solvents, penetration enhancers, solubilizers, and adjuvants.Such compositions are prepared by methods well known in the pharmaceutical field.See, for example, Remington's Pharmaceutical Sciences, Mace Publishing Co., Philadelphia, Pa. 17th Edition (1985); and Modern Pharmaceutics, Marcel Dekker, Inc. 3rd Edition (Edited by G.S. Banker & C.T. Rhodes).

[0102] The pharmaceutical composition (or the crystalline or crystalline salt forms described herein) can be administered alone or in combination with other therapeutic agents. In some embodiments, the other therapeutic agent is a hemoglobin regulator. In some embodiments, the other therapeutic agent is useful for treating sickle cell disease. In some embodiments, the other therapeutic agent is useful for treating complications of sickle cell disease. Non-limiting examples of complications of sickle cell disease include iron overload, pain, infection, acute chest syndrome, stroke, and pulmonary hypertension. In some embodiments, the other therapeutic agent is hydroxyurea, L-glutamine, crizanlizumab, or deferiprone.

[0103] Some embodiments provide a pharmaceutical composition comprising a crystalline form described herein or a crystalline salt form described herein and a pharma- ceutically acceptable excipient.Some embodiments provide a pharmaceutical composition comprising a therapeutically effective amount of a crystalline form described herein or a crystalline salt form described herein and a pharma- ceutically acceptable excipient.

[0104] In some embodiments, the pharmaceutical composition comprises a crystalline form selected from Form I of Compound I, material II of Compound I, HCl Form A of Compound I, besylate Form A of Compound I, edisylate Form A of Compound I, edisylate material B of Compound I, esylate Form A of Compound I, esylate Form B of Compound I, napadilate Form A of Compound I, napadilate material B of Compound I, napsylate Form A of Compound I, napsylate material B of Compound I, oxalate material A of Compound I, oxalate Form B of Compound I, sulfate Form A of Compound I, and tosylate Form A of Compound I, and one or more pharma- ceutically acceptable carriers.

[0105] Some embodiments provide a pharmaceutical composition comprising a pharma- ceutically acceptable excipient, a crystalline form described herein or a crystalline salt form described herein, and another therapeutic agent.

[0106] In some embodiments, the pharmaceutical composition comprises Compound I, wherein at least 95% of Compound I is a crystalline form described herein. In some embodiments, the pharmaceutical composition comprises Compound I, wherein at least 95% of Compound I is Form I. In some embodiments, the pharmaceutical composition comprises Compound I, wherein at least 95% of Compound I is HCl Form A of Compound I, oxalate Form B of Compound I, or sulfate Form A of Compound I.

[0107] In some embodiments, the pharmaceutical composition comprises Compound I, wherein at least 97% of Compound I is a crystalline form described herein. In some embodiments, the pharmaceutical composition comprises Compound I, wherein at least 97% of Compound I is Form I. In some embodiments, the pharmaceutical composition comprises Compound I, wherein at least 97% of Compound I is Material II. In some embodiments, the pharmaceutical composition comprises Compound I, wherein at least 97% of Compound I is HCl Form A of Compound I, oxalate Form B of Compound I, or sulfate Form A of Compound I.

[0108] In some embodiments, the pharmaceutical composition comprises Compound I, wherein at least 99% of Compound I is a crystalline form described herein. In some embodiments, the pharmaceutical composition comprises Compound I, wherein at least 99% of Compound I is Form I. In some embodiments, the pharmaceutical composition comprises Compound I, wherein at least 99% of Compound I is Material II. In some embodiments, the pharmaceutical composition comprises Compound I, wherein at least 99% of Compound I is HCl Form A. In some embodiments, the pharmaceutical composition comprises Compound I, wherein at least 99% of Compound I is HCl Form A of Compound I, oxalate Form B of Compound I, or sulfate Form A of Compound I.

[0109] In some embodiments, the pharmaceutical composition comprises Compound I, wherein at least 99.5% of Compound I is a crystalline form described herein. In some embodiments, the pharmaceutical composition comprises Compound I, wherein at least 99.5% of Compound I is Form I. In some embodiments, the pharmaceutical composition comprises Compound I, wherein at least 99.5% of Compound I is HCl Form A of Compound I, oxalate Form B of Compound I, or sulfate Form A of Compound I.

[0110] In some embodiments, the pharmaceutical composition comprises Compound I, wherein at least 99.9% of Compound I is a crystalline form described herein. In some embodiments, the pharmaceutical composition comprises Compound I, wherein at least 99.9% of Compound I is Form I. In some embodiments, the pharmaceutical composition comprises Compound I, wherein at least 99.9% of Compound I is HCl Form A of Compound I, oxalate Form B of Compound I, or sulfate Form A of Compound I.

[0111] The pharmaceutical composition can be administered in either single or multiple doses.The pharmaceutical composition can be administered by various methods, including, for example, rectal, buccal, intranasal, and transdermal routes.In certain embodiments, the pharmaceutical composition can be administered by intraarterial injection, intravenously, intraperitoneally, parenterally, intramuscularly, subcutaneously, orally, topically, or as an inhalant.

[0112] One mode of administration is parenteral administration, for example, by injection. Forms in which the pharmaceutical compositions described herein can be incorporated for administration by injection include, for example, aqueous or oily suspensions or emulsions, including sesame oil, corn oil, cottonseed oil, or peanut oil, as well as elixirs, mannitol, dextrose, or sterile aqueous solutions, and similar pharmaceutical vehicles.

[0113] Oral administration may be another route for administration of the solid forms described herein, or salts or solvates thereof. Administration may be, for example, via capsules or enteric-coated tablets. When preparing pharmaceutical compositions containing at least one of the solid forms described herein, or salts or solvates thereof, the active ingredient is usually diluted by an excipient and / or enclosed in such a carrier, which may be in the form of a capsule, sachet, paper, or other container. When an excipient functions as a diluent, it may be in the form of a solid, semi-solid, or liquid material, which acts as a vehicle, carrier, or medium for the active ingredient. Thus, the composition may be in the form of a tablet, pill, powder, lozenge, sachet, cachet, elixir, suspension, emulsion, solution, syrup, aerosol (in solid or liquid medium), for example, ointment containing up to 10% by weight of the active ingredient, soft and hard gelatin capsules, sterile injection solution, and sterile packaged powder.

[0114] Some examples of suitable excipients include lactose, dextrose, sucrose, sorbitol, mannitol, starch, gum acacia, calcium phosphate, alginate, tragacanth, gelatin, calcium silicate, microcrystalline cellulose, polyvinylpyrrolidone, cellulose, sterilized water, syrup, and methylcellulose.The formulation can further include lubricants such as talc, magnesium stearate, and mineral oil; wetting agents; emulsifying and suspending agents; preservatives such as methyl and propylhydroxybenzoates; sweeteners; and flavoring agents.

[0115] The composition comprising at least one solid form, or salt or solvate thereof, described herein, can be formulated to provide rapid, sustained, or delayed release of active ingredient after administration to a subject by using procedures known in the art. Controlled release drug delivery systems for oral administration include osmotic pump systems and dissolution systems that contain polymer-coated reservoirs or drug-polymer matrix formulations. Examples of controlled release systems are shown in U.S. Patent Nos. 3,845,770; 4,326,525; 4,902,514; and 5,616,345. Other formulations for use in the methods disclosed herein use transdermal delivery devices ("patches"). Such transdermal patches can be used to inject the solid form, or salt or solvate thereof, described herein, in a controlled amount, continuously or discontinuously. The construction and use of transdermal patches for delivery of pharmaceutical agents is well known in the art. See, for example, US Patent Nos. 5,023,252, 4,992,445, and 5,001,139. ​​Such patches may be constructed for continuous, pulsatile, or on demand delivery of pharmaceutical agents.

[0116] To prepare solid compositions such as tablets, the primary active ingredient can be mixed with pharmaceutical excipients to form solid preformulation compositions containing a homogenous mixture of the solid forms described herein, or salts or solvates thereof. These preformulation compositions are referred to as homogenous, in that the active ingredient is evenly dispersed throughout the composition, allowing the composition to be readily subdivided into equally effective unit dosage forms, such as tablets, pills, and capsules.

[0117] The tablets or pills of the solid forms described herein or their salts or solvates can be coated or otherwise compounded to provide a dosage form that provides the advantage of prolonged action or to protect against the acidic conditions of the stomach.For example, the tablet or pill can comprise an inner dosage component and an outer dosage component, the latter being in the form of an envelope over the former.These two components can be separated by an enteric layer that serves to resist disintegration in the stomach and allows the inner component to enter the duodenum intact or to be delayed in release.Various materials can be used for such enteric layers or coatings, including many polymeric acids and mixtures of polymeric acids with materials such as shellac, cetyl alcohol, and cellulose acetate.

[0118] Compositions for inhalation or insufflation can include solutions and suspensions in pharma- ceutically acceptable aqueous or organic solvents or mixtures thereof, as well as powders. Liquid or solid compositions can contain suitable pharma- ceutically acceptable excipients as described herein. In some embodiments, the compositions are administered by oral or nasal respiratory routes for local or systemic effect. In other embodiments, compositions in pharma- ceutically acceptable solvents can be nebulized by use of inert gases. A nebulized solution can be inhaled directly from the nebulizing device, or the nebulizing device can be attached to a face mask tent or intermittent positive pressure breathing machine. Solution, suspension, or powder compositions can be administered, preferably orally or nasally, from a device that delivers the formulation in an appropriate manner.

[0119] 4. Administration The particular dosage level of the solid forms of the present application or salts or solvates thereof for any particular subject will depend on a variety of factors, including the activity of the particular solid form used, age, body weight, general health, sex, diet, time of administration, route of administration, and rate of excretion, drug combination, and the severity of the particular disease in the subject being treated. For example, dosages can be expressed as milligrams of the solid forms described herein or salts or solvates thereof per kilogram of subject body weight (mg / kg). Dosages of about 0.1-150 mg / kg may be appropriate. In some embodiments, about 0.1-100 mg / kg may be appropriate. In other embodiments, dosages of 0.5-60 mg / kg may be appropriate. Normalization according to subject body weight is particularly useful when using solid forms for both children and adults, or when adjusting dosages between subjects of widely differing sizes, such as occurs when translating effective dosages in non-human subjects, such as dogs, to dosages appropriate for human subjects.

[0120] 5. Method "Treatment" or "treating" is an approach to obtain beneficial or desired results, including clinical results. Beneficial or desired clinical results may include one or more of the following: a) inhibiting a disease or condition (e.g., reducing one or more symptoms resulting from a disease or condition and / or reducing the severity of the disease or condition); b) delaying or preventing the onset of one or more clinical symptoms associated with a disease or condition (e.g., stabilizing a disease or condition, preventing or slowing the progression or worsening of a disease or condition, and / or preventing or slowing the spread (e.g., metastasis) of a disease or condition); and / or c) relieving the disease, i.e., causing regression of clinical symptoms (e.g., improving the disease state, providing partial or total remission of a disease or condition, enhancing the effect of other drug treatments, slowing the progression of a disease, improving quality of life, and / or prolonging survival).

[0121] "Prevention" or "preventing" refers to any treatment of a disease or condition that keeps the clinical symptoms of the disease or condition from developing. The solid forms described herein, or salts or solvates thereof, in some embodiments, can be administered to subjects (including humans) at risk for or who have a family history of a disease or condition.

[0122] "Subject" refers to an animal, such as a mammal (including a human), that has been or will be the object of treatment, observation, or experiment. The methods described herein may be useful in human therapy and / or veterinary applications. In some embodiments, the subject is a mammal. In some embodiments, the subject is a human.

[0123] The term "therapeutically effective amount" or "effective amount" of a solid form described herein, or a salt or solvate thereof, refers to an amount sufficient to effect treatment when administered to a subject and provide a therapeutic benefit, such as amelioration of symptoms or delay of disease progression. For example, a therapeutically effective amount may be an amount sufficient to reduce the symptoms of sickle cell disease. The therapeutically effective amount may vary depending on the subject and the disease or condition being treated, the weight and age of the subject, the severity of the disease or condition, and the method of administration, but can be readily determined by one of ordinary skill in the art.

[0124] The methods described herein can be applied to in vivo or ex vivo cell populations. "In vivo" means within a living individual, such as within an animal or human body. In this context, the methods described herein can be used therapeutically in an individual. "Ex vivo" means outside a living individual. Examples of ex vivo cell populations include in vitro cell cultures and biological samples, including bodily fluid or tissue samples obtained from an individual. Such samples can be obtained by methods well known in the art. Exemplary biological fluid samples include blood, cerebrospinal fluid, urine, and saliva. In this context, the forms described herein and compositions described herein can be used for a variety of purposes, including therapeutic and experimental purposes. For example, the forms described herein and compositions described herein can be used ex vivo to determine optimal dosing schedules and / or dosages of the disclosed forms for a given indication, cell type, individual, and other parameters. Information gathered from such use can be used for experimental purposes or clinically to set up protocols for in vivo treatment. Other ex vivo applications for which the forms described herein and compositions described herein may be suitable are described below or will become apparent to one of skill in the art. Selected forms described herein can be further characterized to determine safety or tolerated dosage in human or non-human subjects. Such properties can be determined using methods commonly known to those of skill in the art.

[0125] The term "hemoglobin," as used herein, refers to any hemoglobin protein, including normal hemoglobin (HbA) and abnormal hemoglobins such as sickle cell hemoglobin (HbS).

[0126] The term "sickle cell disease" refers to diseases mediated by sickle cell hemoglobin (HbS), which is caused by a single point mutation in hemoglobin (Hb). Sickle cell disease includes sickle cell anemia (HbSS), hemoglobin SC disease (HbSC), hemoglobin Sβ plus thalassemia (HbS / β+), and hemoglobin Sβ zero thalassemia (HbS / β0).

[0127] Provided herein is a method for treating sickle cell disease (SCD). Sickle cell hemoglobin (HbS) contains a point mutation in which glutamic acid is replaced by valine, which makes HbS prone to polymerization under hypoxic conditions, resulting in the characteristic sickle shape of HbS-containing red blood cells. Sickle red blood cells are also stiffer than normal red blood cells, and their lack of flexibility can cause vascular blockage. Because polymerization occurs only in deoxygenated conditions under hypoxic conditions, a therapeutic approach is contemplated to maintain HbS in an oxygenated state.

[0128] In some embodiments, provided herein is a method of increasing the oxygen affinity of hemoglobin S in a subject in need thereof, comprising administering to the subject a solid form described herein, or a salt or solvate thereof, or a pharmaceutical composition described herein.

[0129] In some embodiments, provided herein is a method of increasing the oxygen affinity of hemoglobin S in a subject in need thereof, comprising administering to the subject a crystalline form or crystalline salt form described herein, or a pharmaceutical composition described herein.

[0130] In some embodiments, provided herein is a method of treating a hemoglobin-mediated disorder in a subject in need thereof, comprising administering to the subject a solid form described herein, or a salt or solvate thereof, or a pharmaceutical composition described herein.

[0131] In some embodiments, provided herein is a method of treating a hemoglobin-mediated disorder in a subject in need thereof, comprising administering to the subject a crystalline form or crystalline salt form described herein, or a pharmaceutical composition described herein.

[0132] In some embodiments, the disorder is a hemoglobinopathy, hi some embodiments, the hemoglobin is sickle cell hemoglobin.

[0133] In some embodiments, provided herein is a method of treating sickle cell disease in a subject in need thereof, comprising administering to the subject a solid form described herein, or a salt or solvate thereof, or a pharmaceutical composition described herein.

[0134] In some embodiments, provided herein is a method of treating sickle cell disease in a subject in need thereof, comprising administering to the subject a crystalline form or crystalline salt form described herein, or a pharmaceutical composition described herein. EXAMPLES

[0135] equipment technology X-ray powder diffraction (XRPD) XRPD diagrams were generated using SSCI Pattern Match 3.0.4, unvalidated software.

[0136] XRPD patterns were collected with a PANalytical X'Pert PRO MPD or a PANalytical Empyrean diffractometer using an incident beam of Cu radiation generated using an Optix long-range fine focus source. An elliptical tilted multilayer mirror was used to focus the Cu Kα X-rays through the specimen and onto the detector. Prior to analysis, silicon specimens (NIST SRM 640e or NIST SRM 640f) were analyzed to ensure that the observed position of the Si111 peak matched the NIST certified position. Sample specimens were sandwiched between 3 μm thick films and analyzed in transmission geometry. A beam stop, short anti-scatter extensions, and an anti-scatter knife edge were used to minimize background caused by air. Soller slits for the incident and diffracted beams were used to minimize broadening and asymmetry from axial divergence. Diffraction patterns were collected using a scanning position-sensitive detector (X'Celerator) positioned 240 mm away from the specimen and data collector software v.2.2b or v.5.5.

[0137] reflective geometry XRPD patterns were collected using a PANalytical X'Pert PRO MPD diffractometer using an incident beam of Cu Kα radiation generated using a long-distance finely focused source and a nickel filter. The diffractometer was configured using a symmetric Bragg-Brentano geometry. Prior to analysis, silicon coupons (NIST SRM 640e or NIST SRM 640f) were analyzed to confirm that the observed position of the Si111 peak matched the NIST certified position. Sample coupons were prepared as thin annular layers centered on silicon zero-background substrates. Anti-scatter slits (SS) were used to minimize background caused by air. Soller slits for the incident and diffracted beams were used to minimize spread from axial divergence. Diffraction patterns were collected using a scanning position-sensitive detector (X'Celerator) located 240 mm away from the sample, and data collector software v.5.5.

[0138] Differential Scanning Calorimetry (DSC) DSC was performed using a Mettler-Toledo DSC3+ differential scanning calorimeter. Taul lag adjustments were performed with indium, tin, and zinc. Temperature and enthalpy were adjusted with octane, phenyl salicylate, indium, tin, and zinc. Adjustments were then confirmed with octane, phenyl salicylate, indium, tin, and zinc. Samples were placed in sealed aluminum DSC pans and the weights were accurately recorded. The pans were then inserted into the DSC cell. A weighed aluminum pan configured as the sample pan was placed on the reference side of the cell. The lid of the pan was pierced prior to sample analysis. Samples were analyzed from -30°C to 250°C at 10° / min.

[0139] Cyclic DSC method was heating from -30°C to 100°C, back to -30°C, then heating at 10° / min to 250°C.

[0140] Dynamic Vapor Sorption / Desorption (DVS) Automated vapor sorption (VS) data were collected on a Surface Measurement System DVS Intrinsic instrument or a VTI SGA-100 instrument. Samples were not dried prior to analysis. Sorption and desorption data were collected over the range of 5% to 95% relative humidity (RH) in 10% RH increments under a nitrogen purge. The equilibration criteria used for analysis was less than 0.0100% weight change in 5 minutes with a maximum equilibration time of 3 hours. Data were not corrected for the initial moisture content of the samples.

[0141] Thermogravimetric analysis (TGA) TG analysis was performed using a Mettler-Toledo TGA / DSC3+ analyzer. Temperature and enthalpy adjustments were performed using indium, tin, and zinc, then checked with indium. Balance was checked with calcium oxalate. Samples were placed in open aluminum pans. The pans were sealed, the lids were pierced, and then inserted into the TG furnace. A weighed aluminum pan configured as the sample pan was placed on the reference platform. The furnace was heated under nitrogen. Each sample was heated from ambient to 350° C. at 10° C. / min.

[0142] Ion Chromatography Ion chromatography was performed to quantify the weight percentage of selected anions in each sample. Samples were prepared by dissolving approximately 5-10 mg of sample water.

[0143] Solution-state proton nuclear magnetic resonance ( 1 H NMR) Solution NMR spectra were obtained using an Avance 600 MHz NMR spectrometer. Samples were prepared by dissolving a given amount of sample in DMSO-d6 containing TMS.

[0144] Single crystal data collection Form I of compound I Standard uncertainties are stated in crystallographic bracket notation, e.g., 0.123(4) corresponds to 0.123 ± 0.004. Calculated XRPD patterns were generated for Cu radiation using Mercury, as well as atomic coordinates, space group, and unit cell parameters from the single crystal structure. Atomic displacement ellipsoid diagrams were generated using Mercury. Atoms are represented by anisotropic thermal ellipsoids with 50% probability. The quality of the resulting structure is high, as indicated by the fit residual R of 0.0317 (3.17%). R factors in the range of 2%-6% are said to be the most reliable determined structures.

[0145] Data collection: Approximate dimensions: 0.18 x 0.08 x 0.03 mm 3A colorless plate of , was mounted on the polymer loop in random orientation. Preliminary investigations and data collection were carried out on a Rigaku SuperNova diffractometer equipped with a copper anode microfocus sealed X-ray tube (Cu Kαλ=1.54184 Å) and a Dectris Pilatus3 R 200K hybrid pixel array detector. Lattice constants and orientation matrices for data collection were obtained from least-squares refinement using set angles of 4579 reflections in the range 4.3100°<θ<77.1380°. The space group was determined by the program CRYSALISPRO as P212121 (International Table No. 19). Data were collected at room temperature for a maximum diffraction angle (2θ) of 155.236°.

[0146] Data reduction: Frames were integrated in CrysAlisPro. A total of 8747 reflections were collected, of which 3808 were unique. Lorentzian and polarization corrections were applied to the data. The linear absorption coefficient was 0.860 mm for Cu Kα radiation. -1 An experimental absorption correction using CrysAlisPro was applied. Transmission coefficients ranged from 0.957 to 1.000. A second-order extinction correction was applied. The final coefficient, refined by least squares, was 0.0023(3) (absolute units). The intensities of the equivalent reflections were averaged. The agreement factor for the averaging was 2.55% based on the intensity.

[0147] Single crystal data collection HCl form A of compound I Standard uncertainties are stated in crystallographic bracket notation, e.g., 0.123(4) corresponds to 0.123 ± 0.004. Calculated XRPD patterns were generated for Cu radiation using Mercury, as well as atomic coordinates, space group, and unit cell parameters from the single crystal structure. Atomic displacement ellipsoid diagrams were generated using Mercury. Atoms are represented by anisotropic thermal ellipsoids with 50% probability. The quality of the resulting structure is high, as indicated by the fit residual R of 0.0389 (3.89%). R factors in the range of 2%-6% are said to be the most reliable determined structures.

[0148] Data collection: Approximate dimensions: 0.36 x 0.16 x 0.03 mm 3 A colorless plate of , was mounted on the polymer loop in random orientation. Preliminary investigations and data collection were carried out on a Rigaku SuperNova diffractometer equipped with a copper anode microfocus sealed X-ray tube (Cu Kαλ=1.54184 Å) and a Dectris Pilatus3 R 200K hybrid pixel array detector. Lattice constants and orientation matrices for data collection were obtained from least-squares refinement using set angles of 7034 reflections in the range of 5.0710°<θ<77.0390°. The space group was determined to be P21 (International Table Number 4) by the program CRYSALISPRO. Data were collected at room temperature for a maximum diffraction angle (2θ) of 154.678°.

[0149] Data reduction: Frames were integrated in CrysAlisPro. A total of 10895 reflections were collected, of which 4117 were unique. Lorentzian and polarization corrections were applied to the data. The linear absorption coefficient was 2.004 mm for Cu Kα radiation. -1 An empirical absorption correction using CrysAlisPro was applied. Transmission coefficients ranged from 0.716 to 1.000. The intensities of the equivalent reflectances were averaged. The agreement factor for the averaging was 2.67% based on the intensity.

[0150] Example 1 Characterization of amorphous compound I Compound I can be made according to methods known in the art.

[0151] Figure 13 shows the X-ray powder diffraction (XRPD) pattern of amorphous Compound I. A continuous weight loss of approximately 1.9% is observed by TGA up to 203°C (Figure 15). The glass transition (T g Cyclic DSC experiments were performed to measure the T g Indicates T gThe amorphous nature of the material can be characterized by the observation of: Above the glass transition temperature, decomposition rather than recrystallization was observed.

[0152] Dynamic vapor sorption (DVS) isotherms suggest that the material exhibits significant hygroscopicity between 5 and 95% RH (Figure 16). Weight gain upon sorption cycling was approximately 10%. Hysteresis was observed, with a weight loss upon desorption of 7%. Material recovered from the DVS experiments remained amorphous as determined by XRPD.

[0153] Example 2 Preparation of Form I of Compound I A solution of amorphous Compound I in MeCN (>540 mg / mL) was refrigerated for 4 days and then placed in a freezer for 1 day. The solid was filtered and dried under nitrogen to obtain Form I of Compound I.

[0154] Form I of Compound I was also prepared as follows: amorphous Compound I was slurried in ether seeded with Form I of Compound I (prepared as described herein) from a separate experiment at ambient temperature for 1 day to obtain Form I of Compound I.

[0155] Form I of Compound I is anhydrous and begins to melt around 111° C. (FIG. 2A).

[0156] The single crystal structure of form I of compound I was successfully determined. The crystal system is orthorhombic and the space group is P212121. The lattice parameters and calculated volume are a = 5.50599(10) Å, b = 16.4086(2) Å, c = 20.4992(4) Å, α = 90°, β = 90°, γ = 90°, V = 1852.02(5) Å. 3 The formula weight is 386.39gmol -1 , Z=4, and the calculated density is 1.386 gcm -3 Further details of the crystallographic data and crystallographic data collection parameters are summarized in Table 1.

[0157] [Table 1]

[0158] The TGA curve (Figure 3) shows negligible weight loss upon heating to 192°C, consistent with the anhydrous form.

[0159] DSC thermograms were obtained for two different samples of Form I of Compound I. Sample B was crystallized from amorphous Compound I by slurrying in ether at ambient temperature for 1 day with crystal seeds (obtained from amorphous Compound I by slurrying in ether at ambient temperature for 4 days).

[0160] Sample A was obtained by slurrying Form I of Compound I in MeCN for 6 days at ambient temperature. Sample B, shown in FIG. 2B, exhibits an onset of melting at 101° C. In contrast, Sample A was obtained from successive recrystallizations and was white in color, suggesting that this sample was more representative of pure material. Sample A, shown in FIG. 2A, exhibits a higher onset of melting at 111° C. (87 J / g).

[0161] The DVS isotherms suggest that Form I exhibits low hygroscopicity (Figure 4). A total weight gain and loss of 0.7% was observed during the adsorption / desorption cycles without hysteresis. The material recovered from the DVS experiment was identified as Form I of compound I by XRPD.

[0162] Example 3 Preparation of Material II of Compound I Compound I Form I was dissolved in DCM and the solution was added to heptane. The resulting suspension was stirred at ambient temperature for 3 days and then refrigerated for 8 days to give compound I Material II.

[0163] Compound I was also dissolved in EtOAc and concentrated to an oil. The residue was seeded with Compound I material II prepared as above and MTBE was added. The cloudy mixture was stirred at ambient temperature for 7 days. The slurry was concentrated by fast evaporation. The residue was treated with MTBE to give Compound I material II.

[0164] Material II of compound I is anhydrous and begins to melt at around 102° C. (FIG. 6).

[0165] A representative XRPD pattern of material II of compound I is shown in Figure 5. The data suggests that material II is a unique crystalline phase. However, despite attempts, it was not possible to index the XRPD pattern of material II to confirm phase purity.

[0166] The TGA curve (Figure 7) shows negligible weight loss upon heating to 195°C, consistent with the anhydrous form.

[0167] The DSC curve (Figure 6) shows a single endotherm (65 J / g) with an onset near 102°C.

[0168] The DVS isotherms suggest that material II exhibits significant hygroscopicity above 85% RH (Figure 8). The weight gain and loss due to sorption / desorption cycling was approximately 3.4%, with the majority of the weight change occurring above 85% RH. Hysteresis was evident during desorption. The material recovered from the DVS experiment was identified by XRPD as compound I, material II.

[0169] Material II was observed less frequently than Form I and only from kinetic experiments (solvent / antisolvent addition).

[0170] Example 4 Mutual conversion research Binary interconversion slurry experiments between Compound I Form I and Compound I Material II in various solvent systems at room temperature are summarized in Table 2. Saturated solutions were made and then added to a mixture consisting of approximately equal amounts of the two polymorphs. Samples were slurried for several days and solids were collected and analyzed by XRPD. High temperature experiments were attempted, but the solvents had limited solubility and no conversion occurred within the time period evaluated. The results of the room temperature interconversion studies establish that Form I is the most thermodynamically stable form compared to Material II.

[0171] [Table 2]

[0172] Example 5 Preparation of HCl Form A of Compound I To a solution of 79.2 mg of amorphous Compound I in 0.5 mL of THF was added a molar equivalent of HCl in THF. The resulting solid was filtered to form HCl Form A of Compound I.

[0173] An amber solution was made with 1.09 g of amorphous Compound I in 3 mL of tetrahydrofuran. The Compound I solution was stirred at 250 RPM (magnetic stir bar) and seeded with Compound I HCl Form A (made according to the paragraph above). An acidic solution was made with 0.213 mL of 37% HCl in 2 mL of tetrahydrofuran (molar equivalent) and then slowly added to the seeded Compound I solution. Precipitation was observed immediately. After approximately 15 minutes, the solid was collected by vacuum filtration, rinsed with 2 mL of tetrahydrofuran, and dried under vacuum overnight to obtain 1.10 g of Compound I HCl Form A.

[0174] HCl form A of compound I is anhydrous and has an onset of melting around 193 °C. The single crystal structure of HCl form A has been successfully determined. The crystal system is monoclinic and the space group is P21. The lattice parameters and calculated volume are a = 7.72088(10) Å, b = 7.57161(10) Å, c = 17.6273(2) Å, α = 90°, β = 98.0066(12)°, γ = 90°, V = 1022.44(2) Å. 3 The formula weight is 422.85gmol. -1 , Z=2, and the calculated density is 1.376 gcm -3 Further details of the crystallographic data and crystallographic data collection parameters are summarized in Table 3.

[0175] [Table 3]

[0176] TGA data for Compound I HCl Form A shows a 0.6% weight loss upon heating to 188° C. (FIG. 11). DSC shows a single endotherm with an onset near 193° C. (FIG. 10). DVS isotherms suggest the material exhibits significant hygroscopicity (FIG. 12). A 3% weight gain was observed during the sorption cycle, most of which occurred at RH above 85%. A 3.3% weight loss was observed upon desorption. The material recovered from the DVS experiment remained Compound I HCl Form A by XRPD. Compound I HCl Form A was stressed at 40° C. / 75% RH for 27 days. The material was observed to be a free-flowing powder after removal and no change was observed in the XRPD pattern.

[0177] Example 5 Salt Screen Alternative Preparation of Form I of Compound I and Salt Screen of Compound I (R)-(2-(2-((tert-butyldiphenylsilyl)oxy)ethyl)pyridin-3-yl)(3-(hydroxymethyl)morpholino)methanone can be synthesized according to the methods described in U.S. Pat. No. 10,683,285, or U.S. Provisional Patent Application No. 63 / 188,735, filed May 14, 2021, entitled "Methods of Making a Modulator of Hemoglobin," or the PCT application filed the same day herewith, entitled "Methods of Making a Modulator of Hemoglobin," all of which are incorporated herein by reference in their entireties.

[0178] A 50 L reactor was charged with a THF solution of (R)-(2-(2-((tert-butyldiphenylsilyl)oxy)ethyl)pyridin-3-yl)(3-(hydroxymethyl)morpholino)methanone (6.07 kg in about 30 L of THF), 2,6-dihydroxybenzaldehyde (1.2 eq.), and triphenylphosphine (1.3 eq.). The resulting mixture was warmed to 30° C. To the mixture was added a THF solution of DIAD (1.3 eq. in about 9 L of THF) dropwise while maintaining the temperature between 25° C. and 35° C. The reaction mixture was stirred at 30° C. for 30 min. Water (0.6 eq.) was added to the reaction mixture and the mixture was stirred at 30° C. for an additional 1 h.

[0179] To the reaction mixture was added a THF solution of TBAF (0.5 eq., 1M solution in THF) and the mixture was stirred for 18 h. The reaction mixture was concentrated to remove most of the THF under vacuum while maintaining the temperature below 50° C. To the residue was added 1.2 N aqueous HCl (ca. 72 L) and toluene (ca. 30 L). The mixture was stirred at 20° C. for 15 min and the layers were separated. The aqueous layer was extracted twice with toluene (ca. 30 L per extraction). To the aqueous solution was added DCM (ca. 90 L) and potassium carbonate was added to the mixture until the pH was between pH 8 and pH 10. The layers were separated. The DCM solution was washed with water (ca. 30 L) and concentrated under reduced pressure.

[0180] The residue was purified by silica gel chromatography (30 kg silica gel, 100:20:8 mixture of ethyl acetate:DCM:methanol as eluent) to give crude (S)-2-hydroxy-6-((4-(2-(2-hydroxyethyl)nicotinoyl)morpholin-3-yl)methoxy)benzaldehyde.

[0181] Crude (S)-2-hydroxy-6-((4-(2-(2-hydroxyethyl)nicotinoyl)morpholin-3-yl)methoxy)benzaldehyde (4.4 kg, 11.4 mol) as an oil was dissolved in EtOAc (9.11 L). To the resulting solution, seed crystals of compound I form I (prepared as described herein) were added and the reaction mixture was stirred at 15° C.-25° C. for 18 hours. The resulting slurry was heated to 35° C.-45° C. and stirred for 18 hours. MTBE (52.8 L) was added to the slurry and the mixture was stirred for 18 hours while maintaining the temperature at 35° C.-45° C. The slurry was cooled to 15° C.-25° C. and stirred for 18 hours. The solid was collected by filtration, washed with MTBE (2.2 L) and dried under vacuum at 35° C.-45° C. This afforded compound I form I.

[0182] Crystalline salts and co-crystals of compound I were then prepared using 55 acidic and neutral coformers. Approximately 115 experiments were performed (data not shown). The products obtained from the experiments were qualitatively evaluated for crystallinity by PLM and / or XRPD.

[0183] In addition to the HCl salt described herein, 13 unique crystalline materials and forms were obtained from eight different acids, including benzenesulfonic acid, 1,2-ethanedisulfonic acid, ethanesulfonic acid, 1,5-naphthalenedisulfonic acid, naphthalene-2-sulfonic acid, oxalic acid, sulfuric acid, and p-toluenesulfonic acid. All remaining counterions and coformers either failed to provide crystalline materials or provided the free base Form I, the coformer, or a combination of the two.

[0184] Besylate Form A of Compound I Compound I solid (106.2 mg), prepared as described in Example 5, was combined with a benzenesulfonic acid / THF solution (54.4 mg in 0.5 mL of THF). The resulting solution was left to stir at ambient temperature for 3 days to give a thick off-white slurry. The slurry was filtered through a 0.2 μm nylon filter in a Swinnex filter holder. The solid was flushed over the filter with air (5×20 mL). The resulting solid consisted of the besylate salt form A of compound I.

[0185] Compound I besylate form A is a 1:1 besylate salt of Compound I (Figure 17). Compound I besylate form A appears to be a hemi-THF solvate, but the unit cell volume is variable, presumably compensating for differences in solvent content. XRPD patterns (data not shown) show a right shift in the peaks for samples exposed to 44°C under vacuum, which is associated with a decrease in the unit cell volume. The crystal structure is isostructural with Compound I tosylate form A and Compound I esylate forms A and B.

[0186] The stoichiometry of benzenesulfonic acid in the besylate salt form A of compound I was confirmed by solution-state proton nuclear magnetic resonance spectroscopy. The doublet at approximately 6.75 ppm corresponds to one proton of compound I and integrates to 100. The multiplets at approximately 7.6 ppm and 7.31 ppm correspond to five protons of benzenesulfonic acid. These peaks integrate to a total of 484.21. The ratio of compound I / benzenesulfonic acid is 100:96.84 or 1:1 based on the integral per proton. This sample also showed multiplets at approximately 3.60 ppm and 1.75 ppm corresponding to eight protons of THF. These peaks integrate to a total of 367.08. The ratio of compound I / THF is 100:45.89 or 1:0.5 based on the integral per proton.

[0187] Differential scanning calorimetry of the solvated sample showed two small endotherms at 113.9 °C and 129.7 °C (Figure 18). Thermogravimetric analysis showed negligible weight loss up to approximately 85 °C (Figure 19). Two weight loss steps were observed from approximately 85 °C to 211 °C. A 3.9% weight loss was observed from 37 °C to 145 °C. A 6.6% weight loss was observed from 145 °C to 211 °C. The 3.9% weight loss is consistent with 0.3 moles of THF per mole of compound I. This is slightly lower than that observed by NMR due to the variation in unit cell size mentioned above.

[0188] Edisilate Form A of Compound I A solution of 1,2-ethanedisulfonic acid in EtOH (54.1 mg in 1 mL of EtOH) was added to the solid of Compound I (105.1 mg) prepared as described in Example 5. The off-white slurry was stirred for 2 days. After 2 days, the slurry turned pink. The slurry was filtered through a 0.2 μm nylon filter in a Swinnex filter holder. The solid was flushed over the filter with air (5×20 mL). The resulting wet solid consisted of Compound I edisylate Form A.

[0189] Compound I edisylate salt Form A is a metastable 1:1 edisylate salt of Compound I (Figure 20). The sample consisted of a slightly damp pink solid. Although characterized by excess solvent, Compound I edisylate salt Form A is tentatively described as an anhydrate.

[0190] The XRPD pattern of the slightly wet material (data not shown) was successfully indexed with a unit cell volume consistent with an anhydrous 1:1 edisylate salt. The stoichiometry of 1,2-ethanedisulfonic acid in the edisylate salt form A of compound I was confirmed by solution-state proton nuclear magnetic resonance spectroscopy. The doublet at approximately 6.75 ppm corresponds to one proton of compound I and integrates to 100. The singlet at 2.68 ppm corresponds to four protons of 1,2-ethanedisulfonic acid. This peak integrates to 282.188. The ratio of compound I / 1,2-ethanedisulfonic acid is 100:70.547 or 1:0.7 based on the integral per proton. Excess ethanol is evident.

[0191] DSC (Figure 21) and TGA (Figure 22) thermograms of the wet sample showed thermal instability after 91.4° C. A weight loss of 0.8% was observed in the TGA from 39° C. to 91° C. In both experiments the material expanded out of the sample pan upon heating.

[0192] The physical stability of the edisylate salt form A of compound I was investigated. The solid became very sticky when exposed to ambient conditions with a relative humidity level of approximately 57%. This suggests that the edisylate salt form A of compound I is very hygroscopic and not stable under ambient conditions. Drying the wet sample in a vacuum oven at 43 °C indicated physical instability, adding unidentifiable peaks to the X-ray pattern of the resulting material (data not shown). This is likely due to the thermal instability observed when performing differential scanning calorimetry and thermogravimetric analysis, as described above.

[0193] Compound I edisylate material B A THF solution of Compound I solid (99.0 mg in 0.5 mL THF), prepared as described in Example 5, was added to 1,2-ethanedisulfonic acid solid (62.1 mg) and the resulting slurry was allowed to stir at ambient temperature for 2 days to give a clear solution containing a deep orange solid. The solution was decanted with a disposable pipette and the remaining solid was dried briefly under N2. The resulting sticky solid consisted of Compound I edisylate material B.

[0194] Compound I edisylate salt Material B is presumably an anhydrous 1:1 edisylate salt of Compound I (Figure 23).

[0195] The stoichiometry of 1,2-ethanedisulfonic acid in compound I edisylate material B was confirmed by solution-state proton nuclear magnetic resonance spectroscopy. The doublet at approximately 6.75 ppm corresponds to one proton of compound I and integrates to 100. The singlet at 2.68 ppm corresponds to four protons of 1,2-ethanedisulfonic acid. This peak integrates to 484.380. The ratio of compound I / 1,2-ethanedisulfonic acid is 100:121.095 or 1:1.2 based on the integrals per proton.

[0196] Differential scanning calorimetry showed three broad, shallow endotherms at 117.8 °C, 187.3 °C, and 207.8 °C (Figure 24). Thermogravimetric analysis of the dried sample showed a weight loss of 1.1% over the range 46-204 °C (Figure 25). This weight loss is likely due to water, suggesting that this material may also be hygroscopic. This can be further observed by physical stability testing in a vacuum oven at various temperatures (data not shown). Exposing compound I edisylate material B to 44 °C under vacuum yielded compound I edisylate material B with additional unidentified peaks by XRPD. These extra peaks were no longer evident after further drying at 80 °C under vacuum. This unidentified peak is likely the result of compound I edisylate material B absorbing water due to its hygroscopic nature before the XRPD was obtained.

[0197] Essylate Form A of Compound I Compound I solid (107.4 mg), prepared as described in Example 5, was slurried in IPA (2 mL) at ambient temperature. Ethanesulfonic acid (24.5 μL) was added to the slurry. The mixture was stirred for 5 days to obtain a pale pink slurry. The slurry was filtered through a 0.2 μm nylon filter in a Swinnex filter holder. The solid was flushed over the filter with air (5×20 mL). The resulting solid consisted of Compound I esylate Form A.

[0198] Compound I esylate Form A consists of a 1:1 IPA solvate of the esylate salt of Compound I (Figure 26). The IPA stoichiometry varied from analysis to analysis and could not be confirmed. Additionally, the unit cell volume was shown to change, presumably compensating for differences in solvent content. XRPD patterns (data not shown) show a slight shift in the indexed peaks for samples desolvated in a vacuum oven at 44°C, indicating that the unit cell has become slightly smaller. Additional peaks are also evident, suggesting that the solvate is not physically stable. The form is isostructural with Compound I besylate Form A, Compound I esylate Form B, and Compound I tosylate Form A.

[0199] The stoichiometry of ethanesulfonic acid in the esylate salt form A of compound I was confirmed by solution-state proton nuclear magnetic resonance spectroscopy. The doublet at approximately 6.75 ppm corresponds to one proton of compound I and integrates to 100. The quartet at approximately 2.4 ppm and the triplet at approximately 1.07 ppm correspond to five protons of ethanesulfonic acid. These peaks integrate to 632.905. The ratio of compound I / ethanesulfonic acid is 100:126.581 or 1:1.3 based on the integral per proton. This sample also showed a doublet at approximately 1.04 ppm corresponding to six protons of IPA. These peaks integrate to a total of 1794.425. The ratio of compound I / IPA is 100:299.071 or 1:3 based on the integral per proton.

[0200] Differential scanning calorimetry of the solvated sample showed two broad, shallow endotherms at 49.6° C. and 171.6° C., as well as a sharp endotherm at 100.0° C. (FIG. 27). Thermogravimetric analysis showed two weight loss steps from approximately 31° C. to 91° C. and 93° C. to 170° C. (FIG. 28). A 3.8% weight loss was observed from approximately 31° C. to 91° C., and a 17.6% weight loss was observed from approximately 93° C. to 170° C. This is consistent with a loss of 2.1 moles of IPA per mole of Compound I. The discrepancy in IPA content observed in both NMR and TGA further supports that Compound I esylate Form A is a variably solvated salt.

[0201] Essylate Form B of Compound I Compound I solid (128.1 mg), prepared as described in Example 5, was dissolved in acetone (1 mL) at ambient temperature with sonication. Ethanesulfonic acid (29.0 μL) was added to the solution. The solution was stirred for 1 day to obtain an off-white slurry. The slurry was filtered through a 0.2 μm nylon filter in a Swinnex filter holder. The solid was flushed over the filter with air (5×20 mL). The resulting solid consisted of Compound I esylate Form B.

[0202] Compound I esylate form B consists of 1:1 esylate salt of Compound I (Figure 29). Compound I esylate form B also appears isostructural with Compound I esylate form A, Compound I besylate form A, and Compound I tosylate form A. Due to structural similarity with these variable solvates, it is very likely that Compound I esylate form B is a variable hemiacetone solvate. The unit cell volume was shown to compensate for the difference in solvent content by shifting the peaks (data not shown). The physical stability of Compound I esylate form B was also evaluated under 90% relative humidity conditions at ambient temperature. Under these conditions, the sample was deliquescent and therefore highly hygroscopic.

[0203] The stoichiometry of ethanesulfonic acid in the esylate salt form B of compound I was confirmed by solution-state proton nuclear magnetic resonance spectroscopy. The doublet at approximately 6.75 ppm corresponds to one proton of compound I and integrates to 100. The quartet at approximately 2.42 ppm and the triplet at approximately 1.07 ppm correspond to five protons of ethanesulfonic acid. These peaks integrate to 382.97. The ratio of compound I / ethanesulfonic acid is 100:76.594 or 1:0.8 based on the integral per proton. There was also a singlet at 2.09 ppm corresponding to six protons of acetone. This peak integrates to 184.94. The ratio of compound I / acetone is 100:30.823 or 1:0.3 based on the integral per proton.

[0204] Differential scanning calorimetry of the sample showed a slightly broad endotherm with an onset at 97.0° C. (Figure 30). Thermogravimetric analysis showed a slight weight loss of 2.6% over the range from 41° C. to 117° C. (Figure 31), which was calculated to be 0.23 moles per mole of acetone. The discrepancy in acetone content observed in both NMR and TGA further supports the idea that esylate form B of compound I is a variable solvate.

[0205] Napadylate Form A of Compound I A solution of naphthalene-1,5-disulfonic acid in EtOH (95.4 mg in 1 mL of EtOH) was added to the solid of Compound I (98.8 mg) prepared as described in Example 5. The mixture was stirred at ambient temperature for 2 days. After 2 days, the mixture became a pink slurry. The slurry was filtered through a 0.2 μm nylon filter in a Swinnex filter holder. The solid was flushed over the filter with air (5×20 mL). The resulting solid consisted of the napadylate salt Form A of Compound I.

[0206] Compound I napadilate salt Form A consists of a 1:1 ethanol solvate of Compound I napadilate salt (Figure 32). The XRPD pattern of the material was successfully indexed with a unit cell volume consistent with a solvated 1:1 napadilate salt. The ethanol stoichiometry appears to be greater than or equal to 3 mol / mol. The solvate is not physically stable when exposed to 43°C under vacuum, and additional unknown peaks were evident by XRPD within 4 days (data not shown). No significant shifts were observed in the peaks associated with Compound I napadilate salt Form A, suggesting that the solvate is unchanged.

[0207] The stoichiometry of naphthalene-1,5-disulfonic acid in the napadylate salt form A of compound I was confirmed by solution-state proton nuclear magnetic resonance spectroscopy. The doublet at approximately 6.75 ppm corresponds to one proton of compound I and integrates to 100. The doublets at approximately 8.96 ppm and 7.93 ppm and the triplet at approximately 7.41 ppm correspond to six protons of naphthatlene-1,5-disulfonic acid. These peaks are integrated to 449.158. The ratio of compound I / naphthalene-1,5-disulfonic acid is 100:74.90 or 1:0.7 based on the integral per proton. This sample also shows a quartet at approximately 3.45 ppm and a triplet at approximately 1.06 ppm, which correspond to five protons of EtOH. These peaks are integrated to a total of 1754.551. The ratio of compound I / EtOH is 100:350.9 or 1:3.5 based on the integrals per proton.

[0208] Differential scanning calorimetry of the solvated sample showed three broad endotherms at 69.8 °C, 151.0 °C, and 198.4 °C (Figure 33). Thermogravimetric analysis showed three stages of weight loss (Figure 34), consistent with the endotherms observed by DSC. First, a 16.9% weight loss was observed from 30 °C to 117 °C, followed by a 5.9% weight loss from 117 °C to 162 °C, and a 3.7% weight loss from 163 °C to 225 °C. This is consistent with the loss of 3 moles of ethanol per mole of compound I.

[0209] Napadylate of Compound I Material B Compound I solid (98.1 mg) prepared as described in Example 5 was combined with naphthalene-1,5-disulfonic acid / THF solution (50.2 mg in 0.5 mL of THF) and the resulting solution was left to stir at ambient temperature for 2 days to obtain an off-white slurry. The slurry was filtered through a 0.2 μm nylon filter in a Swinnex filter holder. The solid was flushed over the filter with air (5×20 mL). The resulting solid consisted of Compound I napadylate material B.

[0210] Compound I napadylate material B is likely a 1:1 THF solvate of Compound I napadylate (Figure 35). The XRPD pattern of the material did not index well and phase purity could not be confirmed.

[0211] The stoichiometry of naphthalene-1,5-disulfonic acid in the napadylate salt material B of compound I was confirmed by solution-state proton nuclear magnetic resonance spectroscopy. The doublet at approximately 6.75 ppm corresponds to one proton of compound I and integrates to 100. The doublets at approximately 8.85 ppm and 7.90 ppm, and the triplet at approximately 7.4 ppm correspond to six protons of naphthalene-1,5-disulfonic acid. These peaks integrate to 476.767. The ratio of compound I / naphthalene-1,5-disulfonic acid is 100:79.46 or 1:0.8, based on the integrals per proton. This sample also showed multiplets at approximately 3.60 ppm and 1.75 ppm, corresponding to eight protons of THF. These peaks integrate to a total of 813.548. The ratio of compound I / THF is 100:101.69 or 1:1 based on the integral per proton.

[0212] Differential scanning calorimetry of the solvated sample showed two broad endotherms at 77.1 °C and 157.5 °C (Figure 36). Thermogravimetric analysis showed a weight loss of 5.5% over the range from 46 °C to 162 °C (Figure 37), which was calculated to correspond to 0.5 mol per mol of THF.

[0213] Napsylate Form A of Compound I Compound I solid (98.3 mg), prepared as described in Example 5, was combined with a naphthalene-2-sulfonic acid / THF solution (69.0 mg in 0.5 mL of THF) and the resulting solution was left to stir at ambient temperature for 2 days to give a yellow slurry. The slurry was centrifuged and the clear solution was decanted from the yellow solid. The solid was briefly dried under N2. The resulting wet solid consisted of the napsylate salt Form A of Compound I.

[0214] Compound I napsylate salt Form A consists of a 1:1 THF solvate of the napsylate salt of Compound I (Figure 38). The XRPD pattern of the wet material was well indexed as a 1:1 napsylate salt, with the unit cell volume in excess of sufficient to contain at least 1 mol per mol of THF.

[0215] The stoichiometry of naphthalene-2-sulfonic acid in the napsylate salt form A of compound I was shown by solution-state proton nuclear magnetic resonance spectroscopy. The doublet at approximately 6.75 ppm corresponds to one proton of compound I and integrates to 100. The singlet at approximately 8.14 ppm, the multiplets at approximately 7.97 ppm and 7.90 ppm, and the doublet at approximately 7.7 ppm correspond to four protons of naphthalene-2-sulfonic acid. These peaks integrate to 986.947. The ratio of compound I / naphthalene-2-sulfonic acid is 100:246.74 or 1:2.5, based on the integrals per proton. This sample also showed multiplets at approximately 3.60 ppm and 1.75 ppm, corresponding to eight protons of THF. These peaks integrate to a total of 2375.854. The ratio of Compound I / THF is 100:297.0 or 1:3 based on integral per proton. This does not represent the solvent stoichiometry of the napsylate salt Form A of Compound I since the sample was wetted with excess THF.

[0216] Napsyl salt of compound I Material B Compound I solid (120.4 mg) prepared as described in Example 5 was combined with naphthalene-2-sulfonic acid / THF solution (76.5 mg in 1 mL of THF) and the resulting solution was left to stir at ambient temperature for 3 days to obtain an off-white slurry. The slurry was filtered through a 0.2 μm nylon filter in a Swinnex filter holder. The solid was flushed over the filter with air (5×20 mL). The resulting solid consisted of Compound I napsylate material B.

[0217] Compound I napsylate material B consists of a potentially solvated 1:1 napsylate salt of Compound I (Figure 39). The XRPD pattern of the material did not index well and phase purity could not be confirmed. NMR and TGA data suggest a possible THF solvate of up to 0.5 mol / mol.

[0218] The stoichiometry of naphthalene-1,5-disulfonic acid in the napsylate salt material B of compound I was confirmed by solution-state proton nuclear magnetic resonance spectroscopy. The doublet at approximately 6.75 ppm corresponds to one proton of compound I and integrates to 100. The singlet at approximately 8.15 ppm, the multiplets at approximately 7.97 ppm and 7.90 ppm, and the doublet at approximately 7.71 ppm correspond to the seven protons of naphthalene-2-sulfonic acid. These peaks integrate to 1030.08. The ratio of compound I / naphthalene-2-sulfonic acid is 100:147.15 or 1:1.5, based on the integrals per proton. This sample also showed multiplets at approximately 3.60 ppm and 1.75 ppm, corresponding to the eight protons of THF. These peaks integrate to a total of 428.23. The ratio of compound I / THF is 100:53.529 or 1:0.5 based on the integral per proton.

[0219] Differential scanning calorimetry of the sample showed three broad endotherms at 52.0 °C, 110.7 °C, and 177.3 °C (Figure 40). Thermogravimetric analysis showed a 3.0% weight loss from 40 to 117 °C (Figure 41). This weight loss was calculated to be 0.26 moles per mole of THF.

[0220] Compound I Oxalate Material A A solution of oxalic acid in EtOH (23.9 mg in 1 mL of EtOH) was added to the compound I solid (98.8 mg) prepared as described in Example 5. The off-white slurry was stirred for 2 days. The slurry was filtered through a 0.2 μm nylon filter in a Swinnex filter holder. The solid was flushed over the filter with air (5×20 mL). The resulting solid consisted of compound I oxalate material A.

[0221] Compound I oxalate material A likely consists of unsolvated hemi-oxalate salt of Compound I (Figure 42). The XRPD pattern of the material did not index well and phase purity could not be confirmed. Physical stability was not evaluated, but weight loss in thermogravimetric analysis suggests that Compound I oxalate material A is hygroscopic.

[0222] The stoichiometry of oxalic acid in Compound I oxalate material A was confirmed by ion chromatography to contain 0.42 moles of oxalic acid per mole of oxalate ion. Solution-state proton nuclear magnetic resonance spectroscopy was consistent with the chemical structure of Compound I, and no residual organic solvents were observed.

[0223] Differential scanning calorimetry of the sample showed a broad, shallow endotherm at 67.6° C. followed by a sharp endotherm with an onset at 110.9° C. (FIG. 43). Thermogravimetric analysis showed a weight loss of 1.3% over the range 39-122° C. (FIG. 44). This weight loss was likely due to water, as no residual solvent was observed by NMR, suggesting that Compound I oxalate material A may be hygroscopic.

[0224] Oxalate Form B of Compound I A solution of oxalic acid in acetone (26.1 mg in 0.5 mL of acetone) was added to the compound I solid (106.1 mg) prepared as described in Example 5. The clear yellow solution was stirred for 1 day to obtain an off-white slurry. The slurry was filtered through a 0.2 μm nylon filter in a Swinnex filter holder. The solid was flushed over the filter with air (5×20 mL). The resulting solid consisted of the oxalate salt form B of compound I.

[0225] The XRPD pattern of Compound I oxalate Form B (Figure 45) was successfully indexed with a unit cell volume consistent with an unsolvated 1:1 oxalate salt. The physical stability of Compound I oxalate Form B was evaluated under humid conditions. At 90% RH and ambient temperature, the material was primarily Compound I oxalate Form B even after 11 days (data not shown). The XRPD pattern showed one additional peak at 16.96° (2θ).

[0226] The aqueous solubility of the oxalate salt Form B of Compound I was shown to be greater than 134 mg / mL.

[0227] The stoichiometry of oxalic acid in the oxalate salt form B of compound I was confirmed by ion chromatography to be a 1:1 molar ratio of anion to compound I. Solution-state proton nuclear magnetic resonance spectroscopy was used to confirm the chemical structure of compound I. NMR showed no appreciable amounts of residual organic solvent.

[0228] Differential scanning calorimetry of the sample showed a sharp endotherm with an onset at 117.5° C. (FIG. 46). Thermogravimetric analysis showed a weight loss of only 0.2% over the range 49-128° C., consistent with the anhydrous / unsolvated form (FIG. 47). Decomposition then occurred.

[0229] Sulfate Form A of Compound I Compound I solid (99.1 mg), prepared as described in Example 5, was slurried in IPA (2 mL) at ambient temperature. Sulfuric acid (14.5 μL) was added to the slurry. The mixture was stirred for 5 days to obtain a pale pink slurry. The slurry was filtered through a 0.2 μm nylon filter in a Swinnex filter holder. The solid was flushed over the filter with air (5×20 mL). The resulting moist pink solid was further dried in a vacuum oven at 43° C. for 2 days. The dry solid consisted of the sulfate salt Form A of Compound I.

[0230] Compound I sulfate Form A consists of the unsolvated 1:1 sulfate salt of Compound I (Figure 48). The XRPD pattern of the material was successfully indexed with a unit cell volume consistent with the unsolvated 1:1 sulfate salt. Compound I sulfate Form A was shown to be physically stable by XRPD at 43°C under vacuum for 2 days. However, the salt was shown to be hygroscopic and deliquesced within 1 day at ambient temperature and 90% RH.

[0231] Sulfate Form A of Compound I exhibits an aqueous solubility of greater than 87 mg / mL.

[0232] The stoichiometry of sulfuric acid in the sulfate salt Form A of Compound I was confirmed by ion chromatography to be a 1:1 molar ratio to the anion of Compound I. Solution-state proton nuclear magnetic resonance spectroscopy was used to confirm the chemical structure of Compound I. NMR showed no appreciable amounts of residual organic solvent.

[0233] Differential scanning calorimetry of the sample showed a sharp endotherm with an onset at 146.0° C. (FIG. 49). Thermogravimetric analysis observed a weight loss of only 1.4% from 46° C. to 161° C. (FIG. 50). Decomposition then occurred. This weight loss was likely due to water, since no solvent was observed by NMR, suggesting that sulfate Form A of Compound I may be hygroscopic.

[0234] Tosylate Form A of Compound I Compound I solid (92.3 mg) prepared as described in Example 5 was combined with p-toluenesulfonic acid monohydrate / THF solution (46.7 mg in 0.5 mL of THF) and the resulting solution was left to stir at ambient temperature for 3 days to obtain a thick off-white slurry. The slurry was filtered through a 0.2 μm nylon filter in a Swinnex filter holder. The solid was flushed over the filter with air (5×20 mL). The resulting solid consisted of the tosylate salt form A of compound I.

[0235] Compound I tosylate Form A consists of a 1:1 tosylate salt of Compound I (Figure 51). Compound I tosylate Form A appears to be a hemi-THF solvate, but the unit cell volume is variable, presumably compensating for differences in solvent content. XRPD patterns (data not shown) show a right shift in the peaks for samples exposed to 44°C under vacuum, which is associated with a decrease in the unit cell volume. The crystal structure is isostructural with Compound I besylate Form A and Compound I esylate Forms A and B.

[0236] The stoichiometry of p-toluenesulfonic acid in the tosylate salt form A of compound I was confirmed by solution-state proton nuclear magnetic resonance spectroscopy. The doublet at approximately 6.75 ppm corresponds to one proton of compound I and integrates to 100. The doublets at approximately 7.45 ppm and 7.13 ppm, and the singlet at 2.29 ppm correspond to seven protons of p-toluenesulfonic acid. These peaks integrate to a total of 788.20. The ratio of compound I / p-toluenesulfonic acid is 100:112.6 or 1:1.1, based on the integral per proton. This sample also showed multiplets at approximately 3.60 ppm and 1.75 ppm, corresponding to eight protons of THF. These peaks integrate to a total of 400.61. The ratio of compound I / THF is 100:50.08 or 1:0.5 based on the integral per proton.

[0237] Differential scanning calorimetry of the solvated sample showed overlapping broad endotherms at 114.6 °C (Figure 52). A weight loss of 3.3% was observed by TGA over the range 43-137 °C (Figure 53), consistent with 0.3 moles of THF per mole of compound I. The discrepancy in the amount of THF present in NMR and TGA is due to allowed variation in the unit cell, as previously discussed.

[0238] Bioassay The aforementioned crystalline forms can be tested in published assays for biological activity, such as, but not limited to, those described in US Pat. No. 10,683,285.

[0239] All patents and other references cited in this specification are indicative of the level of skill of those skilled in the art to which this disclosure pertains, and are incorporated by reference in their entirety, including any tables and figures, to the same extent as if each reference was individually incorporated by reference in its entirety.

[0240] Those skilled in the art will readily appreciate that the present disclosure is well adapted to obtain the objects and advantages mentioned, as well as those attendant thereto. The methods, variations, and compositions described herein as currently representative of the preferred embodiments are illustrative and are not intended to limit the scope of the disclosure. Modifications therein and other uses will occur to those skilled in the art, which are encompassed within the spirit of the disclosure and defined by the scope of the claims.

Claims

1. having the formula 【Chemistry 1】 Crystals of Form I of Compound I, characterized by X-ray powder diffractograms including 10.8±0.2, 17.3±0.2, 17.5±0.2, 18.3±0.2, 23.4±0.2, 23.7±0.2, and 26.1±0.2 degrees 2θ as determined by a diffractometer using Cu-Kα radiation.

2. 2. A crystalline form I of compound I according to claim 1, characterized by an X-ray powder diffractogram substantially as shown in FIG.

3. 2. The crystalline form I of compound I according to claim 1, characterized by a differential scanning calorimetry (DSC) curve containing an endotherm at about 111°C.

4. 2. A crystalline form I of compound I according to claim 1, characterized by a DSC curve substantially as shown in FIG. 2A.

5. Unit cell parameters: a = 5.50599(10) Å, b = 16.4086(2) Å, c = 20.4992(4) Å, α = 90°, β = 90°, and γ = 90°, and volume = 1852.02(5) Å 3 2. The crystal of Form I of compound I of claim 1, having the formula:

6. having the formula 【Chemistry 3】 Crystals of material II of Compound I characterized by X-ray powder diffractograms including 14.9±0.2, 16.7±0.2, 18.4±0.2, 18.6±0.2, 19.2±0.2, 19.6±0.2, 20.2±0.2, 22.6±0.2, 22.9±0.2 and 25.8±0.2 degrees 2θ as determined by a diffractometer using Cu-Kα radiation.

7. 7. A crystalline material II of compound I according to claim 6, characterized by an X-ray powder diffractogram substantially as shown in FIG.

8. 7. A crystalline material II of compound I according to claim 6, characterized by a differential scanning calorimetry (DSC) curve containing an endotherm at about 102°C.

9. 7. A crystal of material II of compound I according to claim 6, characterized by a DSC curve substantially as shown in FIG.

10. having the formula 【Chemistry 4】 Crystals of Form A of Compound I HCl characterized by X-ray powder diffractograms including 12.7±0.2, 16.4±0.2, 16.7±0.2, 18.5±0.2 and 23.5±0.2 degrees 2θ as determined by a diffractometer using Cu-Kα radiation.

11. 11. The crystalline form A of compound I HCl according to claim 10, characterized by an X-ray powder diffractogram substantially as shown in FIG.

12. 11. The crystalline form A of compound I HCl according to claim 10, characterized by a differential scanning calorimetry (DSC) curve containing an endotherm at about 193°C.

13. 11. The crystalline form A of compound I HCl according to claim 10, characterized by a DSC curve substantially as shown in FIG.

14. A pharmaceutical composition comprising the crystalline form I of compound I of claim 1 and a pharma- ceutically acceptable excipient.

15. 13. A pharmaceutical composition comprising a pharma- ceutically acceptable excipient, the crystalline form I of compound I of claim 1, and another therapeutic agent.

16. A pharmaceutical composition comprising the crystals of Form I of compound I according to claim 1 for increasing the oxygen affinity of hemoglobin S.

17. A pharmaceutical composition comprising the crystals of Form I of compound I according to claim 1 for treating disorders mediated by hemoglobin.

18. 18. The pharmaceutical composition of claim 17, wherein the hemoglobin is sickle cell hemoglobin.

19. A pharmaceutical composition comprising crystalline Form I of compound I of claim 1 for treating sickle cell disease.